The role of m6A modification in spermatogenic dysfunction - Jiale Wang; Xiaobao Zhang; Pingping Tang; Xiaohan Tang; Wenyu Cao; Yang Xu; Suyun Li (Molecular Biology Reports, 2026)

A SIRIUS-Guided Integrative Modificomics and Oligosaccharidomics (SGIMO) strategy unveils bioactive modified metabolites in Chinese rice wine - Chengfeng Gao; Shuxian Yang; Wen Miao; Pingping Dong; Jian-Lin Wu; Na Li (Food Research International, 2026)

Asynchronous recovery of hydrolytic and oxidative enzymes during wetland restoration - Xiangling Zhou; Ting Wang; Lifei Su; Siqi Zheng; Shijia Liu; Yi Liu; Wenhui Quan; Tingting Hu; Jiafang Huang; Yuanbin Cai; Shihua Li; Pingping Guo; et al. (Agriculture, Ecosystems & Environment, 2026)

Gut microbiota-derived metabolites mediate the protective effects of Poria cocos polysaccharide derivatives against oxidative stress - Chunmin Yang; Fenfa Li; Pingping Yan; Xichun Peng (Food Bioscience, 2026)

Multifunctional liquid crystal elastomer conductive foams with self-sensing actuation - Jiajun Li; Guangpeng Wang; Zhibo Zhang; Pingping Min; Yumin Zhang; Tianyu Wang; Kun-LinYang; Jiaqi Zhu (Chemical Engineering Journal, 2026)

The N-terminal region of pdm09/H1N1 PA synergizes with its cognate NP to enhance mammalian adaptation of avian-origin H9N2 canine influenza virus - Yefan Zhou; Pingping Wang; Shiqi Li; Fanyuan Sun; Min Zhu; Rang Wang; Shanshan Dong; Haodong Zhang; Yifeng Qin; Kang Ouyang; Yeshi Yin; Zuzhang Wei; et al. (Veterinary Microbiology, 2026)

Cumulative damage analysis and experimental investigation of transmission tower structures under sequential seismic excitations - Pingping Nie; Haiqing Liu; Saiyu Shao; Zhiwen Yang; Jingrui Li; Siyi He (Soil Dynamics and Earthquake Engineering, 2026)

Nonlinear and scenario-dependent responses of carbon-nitrogen coupling in Chinese dryland soils driven by nitrogen deposition - Chuanqi Wang; Bo Wang; Yuwei Li; Dandan Zhou; Xin Li; Yanan Yu; Nan Lyu; Xuexia Hu; Ke Zhao; Pingping Zhu; Qianqian Qin; Pu Li (Pedobiologia, 2026)

Transcriptomic and proteomic analyses reveal mechanisms of long-term warming acclimation in Phaeocystis globosa - Dayong Liang; Ying Zhang; Huangxin Li; YingYing Wang; Jianping Sun; Zeyu Li; Hua Xiang; Pingping Shen (Harmful Algae, 2026)

Graphene quantum dots-bridged Fe-Ce bimetallic aerogel catalyst for efficient alkaline Fenton removal of three nitrogen species (NH3-N, NO3−-N, and NO2−-N) - Jie Li; Yuxiang Yang; Jining Zhang; Pingping Yao; Yan Huang; Anbang Dai (Environmental Research, 2026)

The recent process and functional applications of inkjet printing in organic solar cells - Shaomeng Li; Pingping Yang; Miaomiao Zhang; Ziwei Zhao; Zhanwei He; Wenxuan Lv; Haining Chen; Qixian Zhang; Mangmang Gao (Chemical Engineering Journal, 2026)

The Characterization and Antifungal Efficacy of NJ-62 Protein from Weizmannia coagulans CGMCC 9951 against Ceratocystis fimbriata - Jia Xu; Xiaohan Liu; Xin Li; Ying Wu; Pengyan Li; Shanshan Tie; Pingping Tian; Shaobin Gu (Probiotics and Antimicrobial Proteins, 2026)

Analysis of snow avalanche dynamics in different types based on numerical simulation: A case study in the northern Himalayas, Tibet - Pingping Zhang; Bin Li; Yang Gao; Haoyuan Gao; Jiawei Wan; Hai Huang (Bulletin of Engineering Geology and the Environment, 2026)

Epigenetic Regulation of Gill Function in Japanese Flounder Under Hypoxic Stress Analyzed via Genome-Wide Methylome and Transcriptome Dynamics - Hengtai Tang; Chengnan Ding; Tianyang Cai; Guangling Li; Pingping Liu; Zhirui Zhang; Feng He (Journal of Ocean University of China, 2026)

Nitroxoline attenuates sepsis-associated pancreatic injury through inhibiting NLRP3-inflammasome mediated pyroptosis - Tingzi Gong; Xiaohui Zeng; Cheng Li; Pingping Liu (Toxicology and Applied Pharmacology, 2026)

Depth-dependent controls on soil saturated hydraulic conductivity in the Loess Plateau - Pingping Zhang; Yunqiang Wang; Hui Sun; Ruijie Li; Jingxiong Zhou; Laiming Huang (Journal of Hydrology, 2026)

Sand barrier microplastics alter plant–soil interactions in artificial sand-fixation areas by constraining plant nutrient utilization - Nan Lu; Bo Wang; Yuwei Li; Dandan Zhou; Yanan Yu; Xin Li; Chuanqi Wang; Pingping Zhu; Qianqian Qin; Ke Zhao; Xuexia Hu; Pu Li (Journal of Arid Environments, 2026)

Machine learning for lithology identification in electrical image logging: A case study of the Chang 73 Sub-Member, Yanchang Formation, East Gansu region, Ordos Basin - Jiaqi Li; Hongping Bao; Shilong Liu; Pingping Shi; Feiming Gao; Liubin Wei; Langlang Wang; Hongyan Yu (Earth Science Informatics, 2026)

Influence of vegetation surface roughness on horseshoe vortex systems in shallow overland flow and erosion mechanisms: Simulation experiments based on HR-PIV - Mengxue Lin; Pingping Yang; Lei Wang; Zhongnian Ban; Zhongfa Zhou; Huilan Zhang; Rui Li (Advances in Water Resources, 2026)

NS1-A53D enhances HA stability to coordinate viral entry with vRNP export and replication during adaptation of H1N1 canine influenza virus - Min Zhu; Rang Wang; Xiaolong Li; Yefan Zhou; Linying Peng; Pingping Wang; Huabo Zhou; Jianni Huang; Yifeng Qin; Kang Ouyang; Yeshi Yin; Zuzhang Wei; et al. (Veterinary Microbiology, 2026)

Dietary supplementation of Radix Isatidis polysaccharides improves meat quality in broilers by regulating lipid metabolism, antioxidant defense, and the gut-muscle axis - Wei Wang; Wenbin Ouyang; Haibo Xiao; Panpan Shi; Pingping Li; Jianguo Zeng; Meirong Song; Sundus Javed; Peng Huang (Research in Veterinary Science, 2026)

Isolation and identification of Fusarium sibiricum as a novel causal agent of root rot in Chamerion angustifolium - Tingting Zhang; Chengsong Liao; Lei Zhang; Zhengnan Li; Pingping Sun (Physiological and Molecular Plant Pathology, 2026)

Morphology, molecular identification, and pathogenicity of two Alternaria species associated with leaf spot of common bistort (Bistorta officinalis Delarbre) in China - Lin He; Jie Zhao; Jianxin Deng; Shanghua Liu; Lei Zhang; Zhengnan Li; Pingping Sun (Physiological and Molecular Plant Pathology, 2026)

Isolation and identification of two causal agents associated with root rot of Scutellaria baicalensis - Lin He; Qianci Chen; Pingping Sun; Lei Zhang; Honghong Jiao; Hongmei Cui; Yuan Yuan; Zhengnan Li (Physiological and Molecular Plant Pathology, 2026)

Species-specific environmental niches govern biogeographic patterns and seasonal dynamics of the harmful algal genus Phaeocystis in Chinese seas - Pingping Shen; Jiayi Shi; Xuejun Fu; Qingshang Song; Yue Xue; Xiyan Wang; Mengqi Dong; Haiping Li (Environmental Pollution, 2026)

Frequency disentanglement with State space gating network for medical image segmentation - Zuo Huang; Xiang Li; Jinyu Cong; Zhenpeng Chen; Pingping Wang; Benzheng Wei (Medical & Biological Engineering & Computing, 2026)

USP9X regulates copper-induced CASP9/CASP3/GSDME-dependent pyroptosis by deubiquitinating JAK1 - Huaduan Zi; Hengcheng Tang; Xiaoxi Yang; Xiaojin Li; Yanmeng Li; Anjian Xu; Qin Ouyang; Sisi Chen; Pingping He; Yanling Li; Qianyu Zhu; Bei Zhang; et al. (Apoptosis, 2026)

Light engineering in aquaculture: physiological responses of Takifugu rubripes larvae to controlled LED irradiance - Xin Li; Songtao Liu; Yafang Liu; Pingping Wei; Yanling Wu; Yingying Fang; Fei Sun; Ying Liu; Yumeng Wu; He Ma (Frontiers in Marine Science, 2026)
Introduction While indoor aquaculture has expanded globally, optimal lighting strategies for fish growth remain understudied. This study aims to establish optimal LED protocols for indoor-reared Takifugu rubripes larvae. Methods T. rubripes larvae were maintained at 50, 250, 500, and 750 mW/m 2 (i50, i250, i500, i750) from hatching through 30 DPH. Growth, gene expression, and enzyme activities were measured. Results Positive growth effects were observed at i250 and i500 within 14–17 DPH, while i50 caused complete mortality after 21 DPH. At 20 DPH, i500 upregulated IGF-1 and BMP2 expression, whereas i50 downregulated BMP4 and SOX9. i50 elevated CTSF, IGM, and HSP70, indicating stress. LPS activity was highest in i250 at 15 DPH, while LDH was lowest in i50. From 10–20 DPH, AKP and ACP were consistently lower in i50. During 5–20 DPH, SOD was suppressed in i750, while T-AOC increased in i250. Discussion Light conditions critically modulate enzymatic activity and early growth in T. rubripes larvae, though underlying mechanisms require further investigation.

Responses of transcriptomic profile to cryopreservation in dwarf surfclam (Mulinia lateralis) sperm - Zhen Xu; Jing Wu; Zujing Yang; Xiaoting Huang; Lisui Bao; Pingping Liu; Xiaoxu Li; Yibing Liu (Cryobiology, 2026)

Bioactive electrospun membrane with DHBA/Zn-MOF for enhancing neurovascular coupling in diabetic wound healing - Manjuan Li; Peng Hua; Linsa Zhou; Lexuan Fang; Pingping Ma; Zixuan Wang; Shicui Jiang; Qiang Zhou; Gaowen Li; Xudong Zheng; Chi Zhang; Litai Jin; et al. (Chemical Engineering Journal, 2026)

Adaptive evolution of thermotolerant xylose-utilizing Saccharomyces cerevisiae for lignocellulosic ethanol production via high-temperature simultaneous saccharification and co-fermentation - Jinchun Lu; Boning Ding; Yuanyuan Lv; Pingping Li; Zhiming Yao; Rui Zhai; Yuanyuan Sha; Zhaoxian Xu; Mingjie Jin (Bioresource Technology, 2026)

A novel aflatoxin B1-degrading strain Bacillus velezensis BV120 and its degrading lactonase - Yalin Li; Cuiping Shao; Ying Wu; Wenyi Kang; Pingping Tian; Shaobin Gu (Journal of Stored Products Research, 2026)

Subchronic exposure to decabromodiphenyl ethane impairs cognitive function and induces neuronal ferroptosis via disruption of mitochondria-associated endoplasmic reticulum membranes - Yuanteng Sun; Fei Xiong; Lingjie Wu; Zhihui Liu; Pingping Liu; Wenhao Li; Juan Zhang; Rongli Sun (Journal of Hazardous Materials, 2026)

Impacts of channel complexity and main-to-anabranch width ratio on fish habitat suitability across varying flow regimes - Pingping Zhou; Hao Zheng; Qianqian Wang; Ruida Wang; Nan Wang; Yongsen Zhang; Yike Li; Zebin Zhang; Li Tian; Zhiyuan Yang; Jiabin Lu; Weiwei Yao (Ecological Engineering, 2026)

Phosphorus limitation drives the deterministic assembly of dissolved organic matter and microbial activity in surface waters of urban lakes - Wei Yu; Pingping Fan; Haiquan Yang; Wenhao Li; Guomin Han; Jifei Hou; Rui Liang; Jingan Chen; Jie Li; Xuede Li (Organic Geochemistry, 2026)

Soil hydraulic pedotransfer functions for estimating saturated hydraulic conductivity: a deep symbolic regression approach with mean shift clustering - Cheng Zhang; Zhongwang Wei; Wei Shangguan; Fan Bai; Wenzong Dong; Qiyun Xiao; Hongwei Zhao; Pingping Liu; Qingliang Li; Yongjiu Dai (Journal of Hydrology, 2026)

Multi-component catalysts with three-dimensional porous structures for exhaust gas purification: Activity for soot and CO - Xiaolong Sheng; Li Li; Changcheng Fu; Peng Zhang; Lefu Yang; Mingzhang Pan; Jinkai Gu; Pingping Huang; Yupei Yang; Tian Zhang; Wei Guan (Journal of Environmental Chemical Engineering, 2026)

Enhanced performance and mechanism of nano-iron-nickel modified substrate in the treatment of compound antibiotic wastewater in constructed wetland - Pingping Duan; Yong Guan; Jian Zhang; Zhijie Han; Hongsen Li; Sen Wang; Fanlong Kong; Yuqian Cui (Journal of Environmental Management, 2026)

Infra-slow body-surface potentials show a group-level association with thyroid cancer - Bohan Deng; Ruili Zhang; Yuxuan Liu; Jinglao Lin; Shicong Gui; Xihao Wei; Yin Cheng; Li Zheng; Shaohua Hu; Pingping Lyu; Yubo Li; Huafen Wang (Journal of Zhejiang University-SCIENCE B, 2026)

PRRSV nucleocapsid and nonstructural proteins dual-regulate CD40 expression via ATF-2 and AP-1 pathways - Chaolun Fu; Hongyan Gao; Yingchao Li; Chang Liu; Yuzhong Zhao; Youbo Li; Zhong Liu; Man Lu; Yang Shen; Yajing Xing; Yu Wang; Xiaotong Wu; et al. (Veterinary Microbiology, 2026)

A 15,000-year Temperature record from the northern boundary of the east asian summer monsoon based on lacustrine brGDGTs - Nan Zhan; Zeyang Zhu; Pingping Li; Luo Wang; Ruilin Wen; Manman Xie; Qing Sun; Guoqiang Chu (Quaternary Science Reviews, 2026)

Variation in methane production since the last deglaciation reconstructed using isoprenoid GDGTs from the sediment of Sihailongwan Maar Lake in northeastern China - Pingping Li; Nan Zhan; Patrick Rioual; Guoqiang Chu; Guibin Zhang; Qi Li; Manman Xie; Guohui Lu; Qing Sun (Quaternary Science Reviews, 2026)

Genomic insights into stepwise selection reshaping fruit traits and male-biased selection driving hermaphroditism in papayas - Changmian Ji; Ruizong Jia; Yuliang Zhang; Xiaoxi Du; Xueying Huang; Huiliang Li; He Dai; Yu Wang; Qian Jiang; Zhengnan Xie; Shanshan Huo; Yang Cao; et al. (Molecular Plant, 2026)

An advanced decoupled polarimetric calibration method for the LuTan-1 hybrid- and quadrature-polarimetric modes - Lizhi Liu; Lijie Huang; Yidi Wang; Pingping Lu; Bo Li; Liang Li; Robert Wang; Yirong Wu (ISPRS Journal of Photogrammetry and Remote Sensing, 2026)

A robust estimation method for canopy chlorophyll content based on FOD and hierarchical weighting combination models - Jie Zhang; Xiaoyu Song; Yuanyuan Ma; Laigang Wang; Liang Sun; Li Li; Heguang Sun; Chunkai Zheng; Pingping Li; Xia Jing; Guijun Yang; Chunjiang Zhao (European Journal of Agronomy, 2026)

Event- and annual-scale precipitation extremes enhance groundwater recharge at the ecological restoration catchment of hilly and gully region - Meina He; Yunqiang Wang; Yali Zhao; Li Wang; Ziliang Zhang; Yi Song; Pingping Zhang; Zimin Li (Ecological Engineering, 2026)

Assessing the Probiotic Properties and safety of Limosilactobacillus reuteri LP4 Isolated from Apis cerana Based on Whole Genome and Phenotype Analyses - Le Xu; Pingping Fang; Mingkui Lv; Shiyu Chen; Chen Liu; Sifan Wang; Jiqin Li; Kun Dong; Qiuye Lin; Zhenhui Cao (Probiotics and Antimicrobial Proteins, 2026)

Visualizing the Landscape and Evolution of Phosphorus Research in Saline-Alkali Soils by Scientometric Analysis - Pingping Zhang; Yuhang Li; Lin Liao; Junna Hu; Genmei Wang; Huanchao Zhang; Jian Xiang (Journal of Soil Science and Plant Nutrition, 2026)

Identification of a putative novel carlavirus infecting Gynura bicolor in China - Lei Xu; Mengze Guo; Pingping Sun; Lei Zhang; Zhengnan Li (Archives of Virology, 2026)

Multi-view field deep learning and data augmentation for heavy metals concentrations prediction in marine sediments based on visible and near-infrared spectroscopy - Xueying Li; Wenzhuo Li; Kai Li; Huimin Qiu; Pingping Fan (Marine Pollution Bulletin, 2026)

Cr-doped CeO2 enables wettability-matched Pt catalysts for nearly complete lignocellulose conversion - Pingping Lu; Weichao Chou; Jun Li; Nan Shi; Lunan Wu; Bin Lou; Jing Wu; Dong Liu (Journal of Environmental Chemical Engineering, 2026)

Microbial generalists and specialists in permafrost demonstrate disparate responses to extreme environments - Chengzhi Mao; Pingping Xu; Ramiro Logares; Bing Ma; Jianchuan Li; Rong Tang; Jiayuan Wang; Xiaosong Wang; Jinglan Wang; Yitong Wang; Yuxiu Chen; Lingyun Chen (Journal of Environmental Management, 2026)

NaCl and light quality reprogram carbohydrate metabolism to modulate growth, quality, and flavor in mustard (Brassica juncea) sprouts - Hongmei Di; Ling Li; Liping Su; Lisha Peng; Ling Rao; Zhifeng Chen; Victor Hugo Escalona; Jing Yang; Yu'nong Zhou; Yong Li; Xuena Yu; Kehao Liang; et al. (Food Chemistry, 2026)

Linking runoff and sediment characteristics to karst development degree in small watershed - Zhengyi Tang; Rui Li; Li Qin; Tao Song; Benjin Yu; Pingping Yang; Jun Jing; Linlv Xiao (CATENA, 2026)

Vertical Distribution and Controls on Heavy Metal(loid)s in Shallow Fissure Soils of Karst Geochemical Background Regions - Liang Tai; Yong Niu; Jia Chen; Gang Li; Pingping Fan; Feng Zhang; Tingjun Tan; Kaiqian Shi (Water, Air, & Soil Pollution, 2026)

Patent analysis of mRNA therapy using deep learning - Yuanqi Cai; Xuejing Zhang; Xiaoming Zhang; Jianxiong Ren; Pingping Wang; Jinyu Cong; Xiang Li; Huali Zuo; Benzheng Wei; Kunmeng Liu (Naunyn-Schmiedeberg's Archives of Pharmacology, 2026)

Effects of nitrogen, phosphorus, iron, and silicon on the growth, total lipid content, and fatty acid composition of the diatom Corethron sp. - Maoyingzang Peng; Pingping Liu; Ruibing Peng; Xiamin Jiang; Sheng Li; Maowang Jiang (Journal of Applied Phycology, 2026)

Genomic evidence reveals temperature-associated ecotypic divergence of Phaeocystis globosa in Chinese coastal waters - Mengqi Dong; Yue Xue; Haiping Li; Dayong Liang; Tao Yang; Yanying Zhang; Pingping Shen (Marine Pollution Bulletin, 2026)

Appetitive traits and their associations with social anxiety and depression in school-aged children: A cross-sectional study - Youxin Wang; Danqi Qiu; Pingping Zhang; Fangjing Shen; Miao Xu; Hui Wang; Li Li (Appetite, 2026)

Group IIId ethylene responsive factor 34 as a positive modulator of ABA signal pathway in Arabidopsis - Li Zhang; Mingxin Piao; Luyao Ji; Zixun Gao; Pingping Wang; Zeng Zhou; Jinpeng Zou; Qingchi Shi; Fang Liu; Yuping Xie; Mingdi Bian; Zhenming Yang; et al. (Plant Science, 2026)

Microbial transformation and mineral precipitation for Cd-Pb-As co-removal with novel PRB materials - Yepu Li; Yanxin Zhang; Mengwei Li; Pingping Xie; Tongcai Wang; Guobing Wang; Hongyan Guo (Journal of Water Process Engineering, 2026)

Uncovering ecological risks of pesticides: From parent compounds to unknown transformation products in soils from Dongting Lake Basin - Lu Liu; Pingping Wang; Feng Li; Xiaoxiao Li; Meng Gao; Yiming Yao; Yu Wang; Zhipeng Cheng; Fei Ge; Hongwen Sun (Journal of Hazardous Materials, 2026)

Investigation of the formation mechanism of mesophase pitch based on the evolution of molecular structure - Yan Yang; Qian Li; Pingping Zuo; Shijie Qu; Fangfang Qin; Wenzhong Shen (Fuel, 2026)

Persistent luminescent nanoparticle-based immunochromatographic assay integrated with a smartphone device for simultaneous detection of aflatoxin B1 and T-2 toxin - Aimei Zhang; Mingzhu Liu; Jingran Sun; Zunquan Zhao; Yonghui Wang; Xiaoli Li; Jin Wu; Yanjun Fang; Pingping Zhang; Jialei Bai (Food Chemistry, 2026)

Machine learning-based response and prediction analysis for gravity-driven membrane - Pingping Zhang; Zihui Xiao; Yonghao Chen; Shaoqiang Nie; Wenzhong Liang; Wenwei Zhong; Tugui Yuan; Huankai Li; Wenxiang Zhang (Desalination, 2026)

OSMAC-activated and GNPS-guided investigation of alkaloids from an endophytic fungus Aspergillus sp. FH-1 of Valeriana officinalis L. - Hao Fan; Pingping Wu; Xin Wang; Yuze Li; Chong Deng; Wei Wang; Xiaomei Song; Xin Zhang; Dongdong Zhang (Biochemical Systematics and Ecology, 2026)

A Fiber-Driven Finite Element Model for Predicting Residual Limb Soft Tissue Deformation: Applications in Prosthetic Socket Design - Ling Wang; Ziyan Qiu; Lei Tang; Fuhao Huang; Pingping Wei; Senay Mihcin; Changning Sun; Hongyuan Zhao; Lei Shi; Song Han; Dichen Li (Annals of Biomedical Engineering, 2026)

SP-DETR: Superior point weak semi-supervised DETR with teacher–student paradigm for crop and weed detection - Yifei Xu; Shuaiqiang Ren; Li Li; Pingping Wei; Hao Deng; Aichen Wang; Yuan Rao (Computers and Electronics in Agriculture, 2025)

RFAGB model: A new machine learning model for microplastic inversion based on remotely sensed data in Bohai Sea - Ao Shen; Yongzheng Ma; Yuan Li; Pingping Hong; Zhiguang Niu; Ying Zhang; Jingen Xiao; Dianjun Zhang (Water Research, 2025)

Extreme climate indices in mountain settlements based on a hierarchical urban–rural classification approach in Qinba, China - Kanhua Yu; Wenting Yang; Juan Xu; Pingping Luo; Xuhui Wang; Zhaoyi Li (Urban Climate, 2025)

Hydrolase-oxidase responses mediate distinct carbon dynamics following wetland conversion to paddy versus upland systems - Lifei Su; Yi Liu; Lishan Tan; Xiangling Zhou; Ting Wang; Yinyin She; Jiafang Huang; Yuanbin Cai; Shihua Li; Pingping Guo; Min Luo (Soil Biology and Biochemistry, 2025)

Development of sustainable active smart Fe-CIT/PVA nanocomposite-based films for monitoring shrimp freshness - Lijun Xia; Pengpeng Wang; Sanwen Zheng; Tingting Zheng; Bin Huang; Heping Li; Zhiming Zou; Pingping Tang; Qun Tang (Food Chemistry, 2025)

Ionic covalent organic framework nanosheets modulated polyamide membranes for augmented ion sieving - Rui Li; Meng He; Shuangqiao Han; Linze Li; Pingping Chen; Xiao Wang; Yuping Tong; Jingli Gong; Huixian Wang; Yatao Zhang; Junyong Zhu (Desalination, 2025)

Synergistic molecular design strategy for near-infrared multi-resonance emitters with accelerated spin-flip - Weibo Cui; Yexuan Pu; Linjie Li; Lixiao Guo; Pingping Zheng; Yun Geng; Chenglong Li (Chemical Engineering Journal, 2025)

Activating V4+/V5+ redox couple in polyanion lattice engineered Na3.1V2(PO4)2.9(SiO4)0.1-CNT by synergistic ionotronic strategy - Anyang Yu; Qi Fan; Zilong Fang; Tian Jiang; Xinxin Wang; Xiedie Zhao; Xiaoshuang Ma; Pingping Sun; Gang Li; Shijun Yuan; Haiyang Zhang; Yining Wang; et al. (Chemical Engineering Journal, 2025)

Deciphering spatial pattern and environmental drivers of deep soil moisture security: insights from integrating spatial non-stationarity in large-scale analysis - Yongping Tong; Yunqiang Wang; Zimin Li; Pingping Zhang; Wei Hu; Jingxiong Zhou; Xiangyu Guo; Hui Sun; Alexis Comber; Ronny Lauerwald (CATENA, 2025)

Iontophoresis-Enhanced Transdermal Delivery of Hyaluronic Acid: Mechanisms, Molecular Weight Effects, and Application Potential - Qinghui Zhang; Dangwei Li; Jian Song; Xianmei Meng; Pingping Zhao; Yihua Zhou; Jun Qian (Journal of Pharmaceutical Innovation, 2025)

Snow-resilient mapping reveals three decades of surface water expansion on the Qinghai–Tibet Plateau - Shaofan Tang; Yilong Peng; Yongzhi Chen; Jiaming Liu; Pingping Zhang; Ying Zhang; Tingting He; Jianhua Li (Remote Sensing Applications: Society and Environment, 2025)

Selective breeding boosts oyster resilience to ocean acidification via energy budget modulation - Xiaoyan Jiang; Xingzhi Zhang; Junliang Guan; Pingping He; Pingyuan Wei; Li Zhang; Jinxia Peng; Liqiang Zhao (Marine Environmental Research, 2025)

Interfacial mechanisms regulating lipid digestion: a systematic study using Tween surfactants with varying structural features - Pingping Zhang; You Li; Zihao Wang; Yang Liu; Zhaoming Ran; Ying Cai; Baocai Xu; Ce Wang (Food Chemistry, 2025)

Cross-food-cultural study of metabolite differences in Asian spicy fermented pastes using combined CIL-LC-MS and GC–MS analysis - Jeonghyun Yun; Chi Zhao; Sunhee Kang; Pingping Zhou; Suyi Zhang; Chang-Won Cho; Zhihua Li; Jang-Eun Lee (Food Chemistry, 2025)

The effect of autophagy activation on apoptosis and myofibrillar structural proteins during the post-mortem storage of Esox lucius - Xuemei Fan; Yibo Liu; Xin Guo; Yabo Wei; Pingping Liu; Hui Li; Xin Chen; Xiaorong Deng; Yongdong Lei; Jian Zhang (Food Chemistry, 2025)

Mobility and dynamics of granular flows in a curved gully: new insights from multi-scale flume experiments - Tiantian Zhang; Bin Li; Yueping Yin; Shaohua Gao; Haoyuan Gao; Pingping Zhang (Landslides, 2025)

Investigating the Potential of CDDO-Me as an HMGB1 Inhibitor in Mitigating Cerebral Ischemia-Reperfusion Injury - Libang Zhang; Guolong Li; Xingru Chen; Tian Li; Richa Raj; Pingping Shen (Journal of Neuroimmune Pharmacology, 2025)

Accumulation, biotransformation and time-dependent transcriptomic responses to PSTs in scallop kidneys - Moli Li; Lingling Kong; Xiaogang Xun; Liang Zhao; Lirong Chang; Huizhen Wang; Zhenmin Bao; Xiaoli Hu; Pingping Liu (Marine Pollution Bulletin, 2025)

Conductive superhydrophobic fabric with dual-induced pH-response for controllable oil-water separation - Xuanjun Li; Xiaojing Su; Junping Liao; Pingping Deng; Zeyuan Lu; Shengye Chen; Kunquan Li; Hongqiang Li; Wenjian Wu (Journal of Environmental Chemical Engineering, 2025)

METTL14 knockdown augmented the polarization of M2-like macrophages to promote acute myeloid leukemia progression - Meng Wang; Zhibin Xie; Yuanyuan Tan; Yan Zhou; Siyi Wang; Pingping Zhang; Jiajia Li (Human Cell, 2025)

Post-exposure recovery of Microcystis aeruginosa from nanoplastics stress: metabolic adaptation and damage resilience - Ruiping Wang; Shizhong Yue; Li Jia; Cevin Tibihenda; Pingping Huang; Zhenghua Li; Di Meng (Frontiers in Marine Science, 2025)
Despite the ubiquitous distribution of nanoplastics (NPs) in global aquatic ecosystems, microbial adaptive strategies during the post-exposure period remain largely unexplored. In this study, Microcystin aeruginosa treated with 5 and 50 mg/L polystyrene (PS) for 15 days and then were transferred to PS-free medium for 15 days to study toxicology and post-exposure effects. The results showed that 5 and 50 mg/L PS inhibited algal growth, with inhibition rates of 6.82% and 9.34% at the end of exposure, respectively, while M. aeruginosa resumed growth on the fourth day of the post-exposure period. In addition, PS enhanced microcystins (MCs) biosynthesis and release in a dose-dependent manner during exposure, while phased variations were observed in MCs production and release during recovery. Transcriptome analysis revealed that 5 mg/L PS inhibited cell growth by disrupting cellular structures, inducing oxidative stress, altering lipid metabolism, and suppressing protein synthesis. These effects were largely reversible during the recovery phase, except for irreversible damage to the algal cell membrane. KEGG pathway analysis identified significant suppression of carbohydrate and energy metabolism during exposure, with subsequent reactivation during post-exposure. These findings suggest that M. aeruginosa may mitigate PS-induced oxidative stress through glucose accumulation and reduced energy expenditure.

Characterization of Cyhalofop-butyl metabolism and identification of resistance genes in Barnyardgrass (Echinochloa crus-galli (L.) P. Beauv.) - Penglei Sun; Liangliang Niu; Xianmin Lan; Pingping Chen; Haiyan Yu; Jingchao Chen; Hailan Cui; Xiangju Li (Pesticide Biochemistry and Physiology, 2025)

Oxidative damage induced by daily exposure to primary and emerging aromatic amines: Insights from large scale biomonitoring and cell-based high-throughput PCR array analysis - Shaohan Zhang; Zijun Zhou; Pingping Wang; Yanan Yao; Yuhao Cao; Jialan Liu; Ping Li; Tao Zhang; Hongkai Zhu; Lei Wang; Hongwen Sun; Zhipeng Cheng (Journal of Hazardous Materials, 2025)

Mechanisms of aristolochic acid I Hepatotoxicity: Central role of PDK4-Induced mitochondrial dysfunction and hepatic inflammation - Zhaobin Wang; Kunyang Li; Xiaoqi Yi; Yichen Wu; Yang Zhao; Pingping He; Qinghua Zeng; Enxiang Zhang (Food and Chemical Toxicology, 2025)

Quantitative assessment of heat tolerance in new rice varieties through field survey during natural extreme heat events - Ting Sun; Tianhui Miao; Jianan Hu; Haoyang Zhou; Minglu Li; Jiayi Zhang; Yuanyuan Pan; Ran Bi; Shenghao Ye; Menglei Wei; Zeyu Wu; Guoqiang Li; et al. (European Journal of Agronomy, 2025)

How does land use transfer affect ecosystem services in Northwest China? - Pingping Zhou; Yuansheng Tian; Jun Zhai; Xiaoyan Song; Yi Li; Wenyi Sun (Ecological Engineering, 2025)

Flower-like Ag/MIL-125-Ti/CoAl-LDH S-scheme heterojunctions toward optimized photothermal-photocatalytic performance - Yuankang Yao; Yi Yang; Zibin Wang; Pingping Liu; Zipeng Xing; Zhenzi Li; Wei Zhou (Chemical Engineering Journal, 2025)

Curcumin-based antibacterial waterborne polyurethane/gelatin composite film for pork preservation and freshness indication - Yuye Zhong; Zhenhong Zhang; Zhengjie Chen; Wenshuo Zhang; Xinghai Liu; Pingping Zhao; Tao Zhang; Houbin Li (Chemical Engineering Journal, 2025)

ATF4 regulates PI3K/AKT signaling axis to promote angiogenesis after myocardial infarction - Pingping He; Weirong Zeng; Jiao Li; Yu Zhang; Ranzun Zhao; Weiwei Liu; Yongchao Zhao; Zhijiang Liu; Changyin Shen; Wei Chen; Yan Wang; Bei Shi (In Vitro Cellular & Developmental Biology - Animal, 2025)

Expanding scales: Achieving prediction of van Genuchten model hydraulic parameters in deep profiles by incorporating broad in situ soil information in pedotransfer functions - Yongping Tong; Yunqiang Wang; Jingxiong Zhou; Xiangyu Guo; Ting Wang; Yuting Xu; Hui Sun; Pingping Zhang; Zimin Li; Ronny Lauerwald (Journal of Hydrology, 2025)

Water consumption turning point for Robinia pseudoacacia occurs at its middle stand age - Yali Zhao; Yunqiang Wang; Ruijie Li; Lijun Qi; Hui Sun; Pingping Zhang; Zimin Li (Plant and Soil, 2025)

BRCA-CN: a blockchain-based framework to support public variant databases sharing in multi-center community for diagnostic reference and China regulatory science - Shoufang Qu; Rongzhi Liu; Shisen Li; Chuanfeng Huang; Yingqian Zhang; Xuan Gao; Pingping Dai; Chao Xu; Rutao Yang; Xuchao Li; Guojun Ouyang; Kang Shao; et al. (Human Genetics, 2025)

Knock Off 3 SlNAIP Genes with Modified CRISPR-Cas9 Causes Dwarf Phenotype in Tomato - Jia Liu; Xinya Dan; Lili Wu; Pingping Fang; Yan Zhang; Xifeng Li; Yanfei Ding (Journal of Plant Biology, 2025)

Unexpectedly stable soil organic carbon in tidal marshes under combined nitrogen loading and increased inundation compared to individual effects - Tianning Fan; Jiafang Huang; Guopeng Liang; Shengen Liu; Dehong Hu; Lifei Su; Yi Liu; YuanBin Cai; Shihua Li; Pingping Guo; Min Luo; Chuan Tong (Limnology and Oceanography, 2025)
Tidal marshes serve as critical carbon (C) sinks, yet face increasing threats from global environmental changes. While previous research has documented how nitrogen (N) loading and sea‐level rise affect total C pools individually, their impacts on soil organic carbon (SOC) stabilization remain critically underexplored, particularly when these factors co‐occur in tidal marsh ecosystems. Through a 3‐yr field experiment, we analyzed how these factors, alone and combined, impact SOC stabilization by examining SOC fraction dynamics. Results showed that N loading increased particulate organic carbon (POC) by 18% and decreased mineral‐associated organic carbon (MAOC) by 13%, reducing SOC stabilization. Conversely, increased inundation raised MAOC by 31% and decreased POC by 19%, promoting SOC stabilization. The decreased MAOC under N loading stemmed from reduced fungal necromass C, while the increased POC related to lower phenol oxidase activity. In contrast, with increased inundation, MAOC rose due to iron‐bound organic C (Fe‐OC) accumulation, while POC declined from increased phenol oxidase activity. When both factors were applied together, SOC stabilization remained at control levels. This occurred because the combined effect maintained oxidative enzyme activities and thus retained POC levels. The simultaneous reduction in fungal necromass C and enhancement of Fe‐OC associations established complementary mechanisms that maintained MAOC at levels equivalent to control. Our findings reveal that N loading and increased inundation drive contrasting patterns of SOC stabilization, while their combination produces uniquely stabilized C dynamics. This insight challenges single‐factor predictions and underscores the importance of multi‐factor experiments in understanding ecosystem responses under concurrent global change scenarios.

Breeding of Gracilariopsis lemaneiformis based on ARTP mutagenesis and low-nutrient screening - Jiaxing Wang; Pingping Li; Yingtang Dong; Shuaipeng Tian; Yuzhen Huang; Ershuai Huang; Anran Shao; Zhenghong Sui (Aquaculture, 2025)

Temperature-dependent shell disease may relate to bacterial community changes of mud crab Scylla paramamosain in RAS - Kaijia Yu; Xiaopeng Wang; Chunlin Wang; Changkao Mu; Yangfang Ye; Pingping Zhan; Ronghua Li; Ce Shi (Aquaculture, 2025)

Divergence of microbial carbon use efficiency and soil organic carbon along a tidal flooding gradient in a subtropical coastal wetland - Ji Tan; Jiafang Huang; Wenhui Quan; Lifei Su; Yi Liu; YuanBin Cai; Shihua Li; Pingping Guo; Min Luo (Water Research, 2025)

Dual signal output detection of acetamiprid residues in medicine and food homology products via nanopore biosensor - Yao Li; Jiyuan Tu; Hong Wang; Kexin Luo; Pingping Xiao; Tangbin Liao; Guo-Jun Zhang; Zhongyue Sun (Food Chemistry, 2025)

Enhanced stabilization and curcumin delivery by covalent NaCas-EGCG modified proso millet protein nanoparticles in Pickering emulsions - Yuting Fan; Jing Ren; Xinyi Li; Pingping Zhang; Yang Yao; Xiuzhu Yu; Shuang-kui Du (Food and Bioproducts Processing, 2025)

Polyploid breeding of Saccharina japonica: Harnessing aposporous reproduction - Pingping Tian; Yan Li; Nianchao Xue; Weiwei Wang; Shuxiu Chen; Yanling Liu; Juan Sun; Guangjin Liang; Juping Zhao; Liang Shi; Nan Zhao; Xia Li; et al. (Aquaculture, 2025)

Corrigendum to “Complete biosynthesis of the potential medicine icaritin by engineered Saccharomyces cerevisiae and Escherichia coli” [Sci. Bull. 66(18) (2021) 1906–1916] - Pingping Wang; Chaojing Li; Xiaodong Li; Wenjun Huang; Yan Wang; Jiali Wang; Yanjun Zhang; Xiaoman Yang; Xing Yan; Ying Wang; Zhihua Zhou (Science Bulletin, 2025)

Temperature variability in northeastern China over the Past 2000 Years: Linkages with the Arctic oscillation and solar activity - Nan Zhan; Fangang Zeng; Qi Li; Manman Xie; Ruixia Hao; Li Pingping; Ruilin Wen; Luo Wang; Qing Sun; Guoqiang Chu (Quaternary International, 2025)

Fe-doped TiO2 nanosheet exposure accelerates the spread of antibiotic resistance genes by promoting plasmid-mediated conjugative transfer - Ping Cheng; Botao Wang; Qianyu Ji; Pingping Yuan; Shixin Gui; Shuying Liang; Lin Li; Hongwei Xu; Shaoqi Qu (Journal of Hazardous Materials, 2025)

Novel multifunctional collagen-based food packaging film incorporating with bilberry anthocyanin for freshness monitoring - Pingping Tang; Yachun Lu; Xia Li; Jing Li; Tingting Zheng (Food Packaging and Shelf Life, 2025)

Removal of dissolved arsenic from deep seawater around hydrothermal vents and seamounts - Yuanchen Li; Guangyong Bo; Yihua Cai; Kan Zhang; Kuanbo Zhou; Pingping Zhang; Chenjing Yang; Tianyu Chen; Minhan Dai; Jian Ma; Zhimian Cao (Earth and Planetary Science Letters, 2025)

Development of a novel LBL@DHBA/Cu-MOF coating on titanium implants to accelerate early osseointegration by promoting neural-vascular-bone coupling regeneration - Peng Hua; Xiaoyi Pan; Jiming Liu; Xuemei Chen; Manjuan Li; Yan Guo; Xuan Li; Pengyuan Leng; Guoyong Fan; Mengjiao Zheng; Kai Yu; Pingping Ma; et al. (Chemical Engineering Journal, 2025)

Unveiling the Characteristics of Microbiota in Different Mucosal Layers of Leopard Coral Grouper (Plectropomus leopardus) - Jiahui Wang; Shengtao Gao; Zhenyuan Xu; Zhihui Yang; Qianqian Mu; Zijian Li; Pingping Liu; Jingjie Hu; Zhenmin Bao (Marine Biotechnology, 2025)

Complete genome sequence and genome organization of Ficus pumila-associated virus, a new putative member of the family Tymoviridae - Mengze Guo; Pingping Sun; Xudong Fan; Jianwei Guo; Lei Zhang; Zhengnan Li (Archives of Virology, 2025)

Human-induced N-P imbalances will aggravate GHG emissions from lakes and reservoirs under persisting eutrophication - Wei Yu; Fali Liu; Xianglan Jiao; Pingping Fan; Haiquan Yang; Yongmei Zhang; Jie Li; Jingan Chen; Xuede Li (Water Research, 2025)

Development and evaluation of high-throughput HD-Marker arrays in pacific white shrimp (Litopenaeus vannamei) - Mingyang Liu; Zhihui Yang; Xin Huang; Qifan Zeng; Qianqian Mu; Zhenyuan Xu; Zijian Li; Pingping Liu; Shi Wang; Jingjie Hu; Zhenmin Bao (Aquaculture, 2025)

Hua Yu Xiao Zheng decoction induces ectopic endometrial stromal cell senescence via inhibiting the PI3K/AKT signaling - Yuan Xu; Yuhui Li; Jingyong Zhang; Pingping Cai (Tissue and Cell, 2025)

Effects of land consolidation intensity on landscape pattern and biodiversity in paddy ecosystem - Pingping Yang; Minzhu Shen; Yan Zhang; Hao Wang; Yinghao Xue; Baoxiong Chen; Jingjun Bian; Pengyao Li; Ti Zhang; Luyu Wang; Meichun Duan (Agriculture, Ecosystems & Environment, 2025)

Study on the Improvement of Coastal Pumping Station Inlet Flow Regime and Evaluation of Transverse Flow Velocity Elimination - Fusheng Lv; Pingping Li; Bo Zhu; Xilong Guo; Lei Wang; Lei Xu (Journal of Marine Science and Engineering, 2025)
Pump station engineering is extensively utilized in water supply and drainage, as well as agricultural irrigation. Due to its geographical advantages and significant comprehensive benefits, the construction of pumping stations in coastal areas has gained substantial attention in recent years. Adverse flow conditions caused by various factors negatively affect the inlet flow regime of pumps, becoming a key factor that restricts the operating life and further development of pump station systems. Optimizing the flow regime in the forebay is crucial for enhancing overall engineering quality, minimizing pump performance degradation, and reducing the risks of cavitation and vibration. This study investigates the flow characteristics of the forebay by combining the Navier–Stokes equations and the k−ε RNG turbulence model. The analysis focuses on the internal flow field, transverse flow before the inlet channel, and the uniformity of flow velocity distribution after the inlet channel. Numerical simulations are validated through physical model tests. We examine the flow characteristics in the forebay, analyze the causes of internal flow disorder, and propose a reasonable and practical rectification scheme for the forebay. Additionally, we elucidate the mechanism of flow state optimization through partition walls. The findings indicate that with the optimal partition wall length, the average elimination rate of transverse flow velocity before the pump station inlet channel reached 48.3%, and the uniformity of flow velocity distribution after the inlet increased by 3.24%. These research findings contribute to mitigating cavitation and vibration in water pump units, providing theoretical support for the safe operation of coastal pumping stations.

Conversion of agricultural waste biomass resource into high-added-value composite and its potential for boosting synergistic removal of ammonia nitrogen in practical water - Junjie Yuan; Yao Zhu; Jizhang Wang; Zhigang Liu; Tao Zhang; Pingping Li; Fengxian Qiu (Food and Bioproducts Processing, 2025)

Improving global soil moisture prediction based on Meta-Learning model leveraging Köppen-Geiger climate classification - Qingliang Li; Xiaochun Jin; Cheng Zhang; Wei Shangguan; Zhongwang Wei; Lu Li; Pingping Liu; Yongjiu Dai (CATENA, 2025)

Evolutionary characteristics and movement process of the January 2023 Duoxiongla snow avalanche, Tibet - Pingping Zhang; Bin Li; Haoyuan Gao; Yang Gao; Jiawei Wan; Shaohua Gao; Haowen Li; Guanzhou Wu; Qingchun Li (Natural Hazards, 2025)

Independent temperature records since the last deglaciation from the varved sediments of Sihailongwan maar lake, northeastern China - Pingping Li; Guoqiang Chu; Patrick Rioual; Nan Zhan; Guibin Zhang; Zeyang Zhu; Li Qi; Manman Xie; Yuan Ling; Qing Sun (Quaternary Science Reviews, 2025)

Corrigendum to “Physiological energetics of selectively bred oysters (Crassostrea hongkongensis) under marine heatwaves” [Mar. Environ. Res. 204 (2025) 106871] - Xiaoyan Jiang; Xingzhi Zhang; Junliang Guan; Pingping He; Pingyuan Wei; Li Zhang; Jinxia Peng; Liqiang Zhao (Marine Environmental Research, 2025)

Physiological energetics of selectively bred oysters (Crassostrea hongkongensis) under marine heatwaves - Xiaoyan Jiang; Xingzhi Zhang; Junliang Guan; Pingping He; Pingyuan Wei; Li Zhang; Jinxia Peng; Liqiang Zhao (Marine Environmental Research, 2025)

Heavy metal concentrations prediction of marine sediments by visible-near infrared spectroscopy based on attention mechanism - Xueying Li; Huimin Qiu; Aizhong Ding; Pingping Fan (Journal of Hazardous Materials, 2025)

Boosting lactic acid photocatalytic synthesis from biomass sugars: The synergistic effect of N-doped carbon dots on ultrathin carbon nitride - Xiao Cao; Xin Wang; Yiyang He; Jixin Li; Haiyan Yang; Pingping Zhang; Songrui Yang; Haixiang Yu; Suyun Xu; Haiping Yuan; Lin Gu (Food Chemistry, 2025)

Influence of topography on the fragmentation and mobility of landslides - Zhaodong Li; Jian Guo; Tonglu Li; Ping Li; Xuetong Ma; Mengmeng Zhang; Enxian Jia; Pingping Xu (Bulletin of Engineering Geology and the Environment, 2025)

Inversion of biophysical parameters of potato based on an active learning pool-based sampling strategy - Yuanyuan Ma; Xiaoyu Song; Jie Zhang; Di Pan; Haikuan Feng; Guijun Yang; Chunxia Qiu; Heguang Sun; Chunkai Zheng; Pingping Li (International Journal of Remote Sensing, 2025)

Morphological, physiological and transcriptional analyses provide new insights into the abnormal phenotype of the macroalga Agarophyton vermiculophyllum (Rhodophyta) - Pingping Li; Jiaxing Wang; Xiaoqing Feng; Jingyu Zhang; Yingtang Dong; Zheng Li; Feng Qin; Yiyi Hu; Zhenghong Sui (Aquaculture, 2025)

Optimizing Strategy for Whole-Genome Genotype Imputation in Scallops - Yujue Wang; Ruixing Yao; Liang Zhao; Qianqian Zhang; Moli Li; Xiangfu Kong; Pingping Liu; Shanhuan Huang; Chen Hu; Zhenmin Bao; Xiaoli Hu (Aquaculture, 2025)

Consistent responses of the shrimp Litopenaeus vannamei gut microbiota to Enterocytozoon hepatopenaei infection across spatially distant farms - Shifeng Xu; Pingping Zhan; Jinquan Li; Jiong Chen; Qiongfen Qiu; Jinbo Xiong (Aquaculture, 2025)

Spectral Analysis of Dissolved Organic Carbon in Seawater by Combined Absorption and Fluorescence Technology - Xuan Cao; Feng Xiong; Yang Wang; Haikuan Ma; Yanmin Zhang; Yan Liu; Xiangfeng Kong; Jingru Wang; Qian Shi; Pingping Fan; Yunzhou Li; Ning Wu (Journal of Marine Science and Engineering, 2024)
Dissolved organic carbon refers to soluble carbon substances in water bodies and can be used as an important indicator for water pollution. Spectroscopic detection is commonly used to detect dissolved organic carbon in seawater. However, independent spectral methods are susceptible to interference, and insufficient extraction of the data features can occur. Accordingly, this study introduces a multisource spectral fusion method that relies on a combination of principal component analysis and convolutional neural networks to construct the detection model. The Bayesian correction method is used for calibration, and the dissolved organic carbon content of 10 groups of unfiltered seawater samples is analyzed. Correcting the spectral data acquired from samples containing impurities significantly improved the linear correlation coefficient R2 of dissolved organic carbon from 0.8891 to 0.9838. Similarly, the mean absolute error was significantly reduced from 15.33% to 3.24%, while the individual absolute error was effectively controlled, remaining within 9%. The obtained results show that the developed method effectively integrates the ultraviolet absorption and fluorescence spectral data and overcomes interference from other substances using the Bayesian correction method. Overall, this provides a highly accurate detection system with potential applications in monitoring the marine environment.

Cu-Co binary metal-organic framework nanosheets for highly efficient degradation of norfloxacin using the Fenton-like process - Long Zhou; Houying Yuan; Hui Li; Songhua Chen; Pingping Zhao; Ruiming Zhang; Zeyang Lu; Zuliang Chen (Journal of Environmental Chemical Engineering, 2024)

Nitrogen deposition enhances accumulation of microbial and plant-derived carbon in forest soils: a global meta-analysis - Chenying Wang; Xiaoyan Li; Meng Zhang; Zichen Han; Yun Xia; Pingping Lian; Liuming Yang; Kai Yue; Yuexin Fan (Plant and Soil, 2024)

Independent induction of calluses and nematophytes from exfronds and their potential application for kelp cultivation and germplasm conservation - Pingping Tian; Weiwei Wang; Yan Li; Guangjin Liang; Juan Sun; Yanling Liu; Guanpin Yang; Xiaojie Li (Journal of Applied Phycology, 2024)

PI3KR1 and AKT1 in largemouth bass (Micropterus salmoides): molecular cloning, characterization, and its involvement in the alleviation of hepatic glycogen deposition caused by insulin inclusion in vitro - Yuru Li; Shiwen Chen; Yijun Liu; Pingping Liu; Songlin Li; Ning Liu (Fish Physiology and Biochemistry, 2024)

Quantitative analysis of impact of human activities on soil erosion using the RUSLE model in a typical karst area in Guizhou, China - Xiong Gao; Zhongfa Zhou; Pingping Yang; Haoru Zhang; Changxin Yang; Shui Li (Environmental Monitoring and Assessment, 2024)

The Chinese version of the Ohkuma questionnaire: reliability analysis and diagnostic value - Zhang Pingping; Lu Dezhi; Li Tingting; Zhang Hui; Liu huan; Wang Xiaowen; Liu Wenbo (Acta Neurologica Belgica, 2024)

Characterizing the uncertainty of CMORPH products for estimating orographic precipitation over Northern California - Zhe Li; Haonan Chen; Robert Cifelli; Pingping Xie; Xiaodong Chen (Journal of Hydrology, 2024)

Distribution mechanisms of soil surface erosion and underground leakage in karst areas of China: A systematic, quantitative review - Jia Chen; Pingping Fan; Feng Zhang; Tingjun Tan; Nufang Fang; Zeyan Wu; Zhongwu Li; Yaojun Liu (CATENA, 2024)

Study on Elastoplastic Damage Constitutive Model and Permeability Evolution Law of Gas-Bearing Coal - Jiale Fu; Bobo Li; Chonghong Ren; Qiaoyun Cheng; Pingping Ye; Sandong Zhou (Rock Mechanics and Rock Engineering, 2024)

Comparisons of stripe rust response, grain yield and quality between fungicide sprayed and non-sprayed treatments for newly developed wheat lines carrying different genes for adult-plant resistance to stripe rust - Hao Chen; Liangqi Zhang; Chuanguang Ding; Yuqi Luo; Guoyun Jia; Junming Feng; Yuqi Wang; Binfan Si; Jianian Zhou; Xin Li; Kebing Huang; Suizhuang Yang; et al. (Crop Protection, 2024)

The general patterns of water flow in loess slope system and implications for slope geological security - Li Feng; Maosheng Zhang; Hao Liu; Bin Zhang; Zhen Du; Pingping Sun; Junbo Bi; Liang Wang; Tianfeng Gu (Science of The Total Environment, 2024)

Exploring the environmental influences and community assembly processes of bacterioplankton in a subtropical coastal system: Insights from the Beibu Gulf in China - Jinxia Peng; Dapeng Wang; Pingping He; Pinyuan Wei; Li Zhang; Wenlu Lan; Yusen Li; Wenjian Chen; Zelong Zhao; Linyuan Jiang; Lei Zhou (Environmental Research, 2024)

Performance of loach to reduce clogging matter in vertical-flow constructed wetlands: Hydraulic evaluation and metabolic processes - Xiuzheng Fu; Fanlong Kong; Pingping Duan; Fanyi Li; Wenxuan Hu; Xiaomin Liu; Zhengda Yu; Yuqian Cui (Chemical Engineering Journal, 2024)

Metabolic Heterogeneity and Potential Immunotherapeutic Responses Revealed by Single-Cell Transcriptomics of Breast Cancer - Shicong Tang; Qing Wang; Ke Sun; Ying Song; Rui Liu; Xin Tan; Huimeng Li; Yafeng Lv; Fuying Yang; Jiawen Zhao; Sijia Li; Pingping Bi; et al. (Apoptosis, 2024)

Seasonal dynamics of antibiotic resistance genes and mobile genetic elements in a subtropical coastal ecosystem: Implications for environmental health risks - Jinxia Peng; Dapeng Wang; Pingping He; Pinyuan Wei; Li Zhang; Wenlu Lan; Xingzhi Zhang; Junliang Guan; Yongxian Chen; Wei Li; Yusi Zheng; Yusen Li; et al. (Environmental Research, 2024)

Bioinspired PEDOT:PSS-PVDF(HFP) flexible sensor for machine-learning-assisted multimodal recognition - Pingping Wu; Lin Li; Songtao Shao; Junchao Liu; Jingxia Wang (Chemical Engineering Journal, 2024)

The effect of Ca2+-calcineurin signaling pathway on the antifungal activity of Pd-D-V against Botrytis cinerea - Yao Yu; Xinru Li; Yiping Hou; Min Wei; Yiyun Qian; Yuxin Zhou; Min Yin; Yanqin Jiang; Pingping Song (Pesticide Biochemistry and Physiology, 2024)

One–third substitution of nitrogen with cow manure or biochar greatly reduced N2O emission and carbon footprint in saline–alkali soils - Sheng Zhang; Lihua Xue; Ji Liu; Pingping Jia; Ying Feng; Yi Xu; Zhijie Li; Xiaoning Zhao (Field Crops Research, 2024)

Analysis of Tidal Current Energy Potential in the Major Channels of the Bohai Strait Based on Delft3D - Pengcheng Ma; Hongyuan Shi; Huaiyuan Xue; Pingping Li; Yongkang Sun (Journal of Ocean University of China, 2024)

Fatty acids metabolism in ozone-induced pulmonary inflammatory injury: Evidence, mechanism and prevention - Mengyuan Li; Xiangbing Kong; Xiaotong Jian; Yacong Bo; Xinyi Miao; Huaiyong Chen; Pingping Shang; Xiaolei Zhou; Ling Wang; Qiao Zhang; Qihong Deng; Yuan Xue; et al. (Science of The Total Environment, 2024)

Phosphorus addition enhances heterotrophic respiration but reduces root respiration in a subtropical plantation forest - Yun Xia; Benjamin L. Turner; Yiqing Li; Pingping Lian; Zhijie Yang; Yuexin Fan; Liuming Yang; Yusheng Yang (Science of The Total Environment, 2024)

Identification of a novel waikavirus infecting Pittosporum tobira in China - Mengze Guo; Lei Zhang; Xudong Fan; Pingping Sun; Jianwei Guo; Zhengnan Li (Archives of Virology, 2024)

Melatonin delays softening of postharvest pepper fruits (Capsicum annuum L.) by regulating cell wall degradation, membrane stability and antioxidant systems - Pingping Li; Ruihao Zhang; Huidan Zhou; Yunrong Mo; Shuang Wu; Xiang Zhang; Zhihe Xie; Tianyu Zhang; Kai Zhao; Junheng Lv; Minghua Deng (Postharvest Biology and Technology, 2024)

Dynamics of solar-induced chlorophyll fluorescence (SIF) and its response to meteorological drought in the Yellow River Basin - Hao Wu; Pingping Zhou; Xiaoyan Song; Wenyi Sun; Yi Li; Songbai Song; Yongqiang Zhang (Journal of Environmental Management, 2024)

Risk assessment and spatial analysis of paralytic shellfish toxin (PST) concentrations and acute dietary exposure of commercially available shellfish in coastal areas in China - Shuwen Li; Jiao He; Jinfang Sun; Feng Pan; Pingping Zhou; Lei Zhang; Xin Yang; Chengbin Cao; Xiaojin Yu; Pei Cao (Food Control, 2024)

NIR-photocatalytic LDHB-mimetic CuS@ZnS nanoenzyme regulates arthritis microenvironment through lactate oxidation and hydrogen evolution - Dezhi Lu; Fan Wu; Kangming Chen; Wentao Li; Pingping Zhang; Yutong Hou; Yingze Su; Weixi Liu; Tianchang Wang; Yihao Liu; Chenglan Huang; Shuo Chen; et al. (Chemical Engineering Journal, 2024)

Edible composite films: enhancing the postharvest preservation of blueberry - Dongfang Shi; Boya Zhao; Pingping Zhang; Ping Li; Xinpei Wei; Kai Song (Horticulture, Environment, and Biotechnology, 2024)

Response of deep soil water deficit to afforestation, soil depth, and precipitation gradient - Jingxiong Zhou; Yunqiang Wang; Ruijie Li; Haoran He; Hui Sun; Zixuan Zhou; Yali Zhao; Pingping Zhang; Zimin Li (Agricultural and Forest Meteorology, 2024)

Interpreting and modelling the daily extreme sediment events in karst mountain watersheds - Jun Jing; Rui Li; Linlv Xiao; Dongcai Shu; Pingping Yang (Science of The Total Environment, 2024)

A novel local grey model considering fluctuation based on kernel function for energy production prediction - Kailing Li; Pingping Xiong; Xinyan Huang; Yan Dong (Journal of Cleaner Production, 2024)

Variations of sediment organic phosphorus and organic carbon during the outbreak and decline of algal blooms in Lake Taihu, China - Jiehua Wang; Xiuling Bai; Wenchao Li; Pingping Zhang; Mengdi Zhang; Haoran Wang; Yingge Bai (Journal of Environmental Sciences, 2024)

Effect of apple high-methoxyl pectin on heat-induced gelation of silver carp myofibrillar protein - Han Yu; Yunfeng Zhao; Runze Li; Xin Guo; Pingping Liu; Jian Zhang (Food Chemistry, 2024)

Analyte-perturbed balance between reducibility and fluorescence of Ti3C2 MXene quantum dots for label-free, dual-mode detection of silver ions - Peng Jin; Pingping Wan; Chunyan Zhang; Xu Li; Yan Wang; Jianxin Luo; Kun Li (Analytica Chimica Acta, 2024)

N-S variations of crustal structure beneath the central Tarim Basin from joint inversion of receiver functions, ambient seismic noise surface wave dispersion, and magnetotelluric data - Miao Peng; Handong Tan; Changhong Lin; Shaoqian Hu; Pingping Wu; Lehong Xu; Chonglong Wang; Yifan Liu; Lihui Wang; Bohao Li (Tectonophysics, 2024)

Enhancing methanol tolerance of Thermomyces lanuginosus lipase by rational design and biodiesel production through one-step feeding of methanol - Pingping Qu; Raudah Lazim; Dongdong Li; Rui Xu; Fei Wang; Xun Li; Yu Zhang (Journal of Cleaner Production, 2024)

Aromatic acids affect the performances of constructed rapid infiltration systems based on red mud and coke: Removal efficiency, electron transport, and metabolism - Shengtao Liu; Pingping Lu; Yunnan Zhang; Shu Gao; Xinjuan Li; Menglin Chen; Yuxiang Lu; Chengyuan Su (Journal of Environmental Chemical Engineering, 2024)

The relationship between maternal exposure to ambient air pollutants and premature rupture of membranes: A systematic review and meta-analysis - Yaxin Liang; Min Li; Qiubo Lyu; Pingping Li; Yuhan Lyu; Yue Yu; Wuqiang Peng (Environmental Pollution, 2024)

A green large-scale fabrication of cellulose-based multifunctional fluorescent fibers for versatile applications - Changjing Qiu; Fang Peng; Pingping Wu; Xijun Wang; Songnan Hu; Chuanlin Huang; Xingxing Li; Dingfeng Xu; Hui Li; Peng-Cheng Ma; Pan Chen; Haisong Qi (Chemical Engineering Journal, 2024)

Identification and functional analysis of a CbSHR homolog in controlling adventitious root development in Catalpa bungei - Ziyuan Hao; Jingyi Liu; Yao Teng; Xinchang Wang; Peiyao Jiang; Weijie Si; Hongying Li; Fuqiang Yang; Pingping Guo; Jiawen Yang (Plant Cell, Tissue and Organ Culture (PCTOC), 2024)

Review on recent advances of Gracilariopsis lemaneiformis (Rhodophyta) - Mengxing Cao; Jingyu Zhang; Pingping Li; Jinguo Wang; Ping Mi; Zhenghong Sui (Algal Research, 2024)

In-situ synthesis of ZIF-8 on magnetic pineapple leaf biochar as an efficient and reusable adsorbent for methylene blue removal from wastewater - Xiaoxiao Ma; Yutong Li; Yile Du; Shuangli Chen; Yunfan Bai; Lin Li; Chuhua Qi; Pingping Wu; Sijing Zhang (Environmental Science and Pollution Research, 2024)

Physiological-biochemical responses and transcriptomic analysis reveal the effects and mechanisms of sulfamethoxazole on the carbon fixation function of Chlorella pyrenoidosa - Yuhao Zhou; Yujiao Yue; Xinyang Chen; Feifan Wu; Wei Li; Pingping Li; Jiangang Han (Science of The Total Environment, 2024)

Ultrafine Ru nanoparticles stabilized by V8C7/C for enhanced hydrogen evolution reaction at all pH - Yanju Long; Yong Shen; Pingping Jiang; Hui Su; Jiahui Xian; Yamei Sun; Jun Yang; Haili Song; Qinghua Liu; Guangqin Li (Science Bulletin, 2024)

Investigation on damage-permeability model of dual-porosity coal under thermal-mechanical coupling effect - Pingping Ye; Bobo Li; Chonghong Ren; Haosheng Song; Jiale Fu; Xuehai Wu (Gas Science and Engineering, 2024)

N-nitrosodimethylamine exposure to zebrafish embryos/larvae causes cardiac and spinal developmental toxicity - Xiaoyi Liu; Jinge Song; Xiaotao Yan; Pingping Li; Jinhua Zhang; Bin Wang; Jing Si; Yong Chen (Comparative Biochemistry and Physiology Part C: Toxicology & Pharmacology, 2024)

Accumulated Endogenous Abscisic Acid Contributes to the Cold Tolerance of Pre-planted Cultivated Tobacco - Qiansi Chen; Pingping Liu; Zefeng Li; Qingxia Zheng; Huina Zhou; Jinyan Liu; Peijian Cao; Ming Fang (Plant Molecular Biology Reporter, 2024)

Optimizing soil carbon content prediction performance by multi-band feature fusion based on visible near-infrared spectroscopy - Xueying Li; Pingping Fan; Huimin Qiu; Yan Liu (Journal of Soils and Sediments, 2024)

Cd-contaminated soil remediation using MgFe2O4/chitosan carbon aerogel beads - Yutong Li; Xiaoxiao Ma; Yile Du; Shuangli Chen; Pingping Wu; Sijing Zhang (Journal of Environmental Chemical Engineering, 2024)

Active and intelligent collagen films containing laccase-catalyzed mulberry extract and pickering emulsion for fish preservation and freshness indicator - Ruimin Ran; Yongming Xiong; Tingting Zheng; Pingping Tang; Yuanzhi Zhang; Changkai Yang; Guoying Li (Food Hydrocolloids, 2024)

Magnetically separable Co0.6Fe2.4O4/MIL-101-NH2 adsorbent for Congo red efficient removal - Zhenhong Zhang; Yuye Zhong; Peng Sun; Pingping Zhao; Houbin Li; Xinghai Liu (Environmental Science and Pollution Research, 2024)

Effects of dietary supplementation with Radix Isatidis polysaccharide on egg quality, immune function, and intestinal health in hens - Panpan Shi; Zenghao Yan; Miaofen Chen; Pingping Li; Deqin Wang; Junjuan Zhou; Zhaojie Wang; Shihao Yang; Zhikun Zhang; Chuyuan Li; Yulong Yin; Peng Huang (Research in Veterinary Science, 2024)

Prediction of dissolved organic nitrogen via spectroscopic fingerprint in the shallow riverbed sediments of effluent-dominated rivers: A case study in Xi’an, northwest China - Yutao Wang; Haojie Yin; Ziyi Wang; Yi Li; Pingping Wang; Longfei Wang (Journal of Hydrology, 2024)

Occurrence, distribution, and ecological risk of heavy metals and veterinary antibiotics in soils from citrus orchards: side effects of organic substitution - Pingping Ye; Kunpeng Gao; Hua Feng; Linfa Fang; Dong Li; Jong-Hwan Park; Yueqiang Zhang; Ran Xiao (Journal of Soils and Sediments, 2024)

Potato late blight severity monitoring based on the relief-mRmR algorithm with dual-drone cooperation - Heguang Sun; Xiaoyu Song; Wei Guo; Mei Guo; Yanzhi Mao; Guijun Yang; Haikuan Feng; Jie Zhang; Ziheng Feng; Jiao Wang; Yuanyuan Ma; Chunkai Zheng; et al. (Computers and Electronics in Agriculture, 2023)

Bisphenol A induced neuronal apoptosis and enhanced autophagy in vitro through Nrf2/HO-1 and Akt/mTOR pathways - Yue Shen; Xinying Li; Hongyan Wang; Yicheng Wang; Liqing Tao; Pingping Wang; Heng Zhang (Toxicology, 2023)

Increase in iron-bound organic carbon content under simulated sea-level rise: A “marsh organ” field experiment - Dehong Hu; Wenjing Lan; Min Luo; Tianning Fan; Xin Chen; Ji Tan; Shihua Li; Pingping Guo; Jiafang Huang (Soil Biology and Biochemistry, 2023)

Exploring the association between air pollution and Parkinson’s disease or Alzheimer’s disease: a Mendelian randomization study - Pingping Ning; Xingzhi Guo; Qiumin Qu; Rui Li (Environmental Science and Pollution Research, 2023)

Porous pillararene-based polymer as adsorbent and solid disinfectant for water treatment - Guizhou Xu; Pingping Yang; Yalan Zhang; Lin Sun; Xuejiao Hu; Wenrui Zhang; Yizhou Tu; Yuansong Tian; Aimin Li; Xianchuan Xie; Xueyuan Gu (Chemosphere, 2023)

Impacts of ecological water supplement projects on fish habitat suitability in a high-leakage river in China - Xueping Gao; Luyao Zhang; Bowen Sun; Jiaxin Li; Pingping Miao; Yunpeng Bai (Journal of Hydrology, 2023)

Dissecting the genetic basis of grain weight and size in common oat by genome-wide association study - Honghai Yan; Di Deng; Pingping Zhou; Yun Peng; Xiaolong Dong; Shuchang Li; Yongjie Zhang; Qin Man; Ziqin Lv; Tao Chen; Changzhong Ren; Yuanying Peng (Journal of Cereal Science, 2023)

Comparative study on the effect of different salts on surimi gelation and gel properties - Yadong Zhao; Ganping Wei; Jiajia Li; Fang Tian; Bin Zheng; Pingping Gao; Rusen Zhou (Food Hydrocolloids, 2023)

An injectable, self-healing, and antioxidant collagen- and hyaluronic acid-based hydrogel mediated with gallic acid and dopamine for wound repair - Changkai Yang; Yuanzhi Zhang; Xiaoxia Zhang; Pingping Tang; Tingting Zheng; Ruimin Ran; Guoying Li (Carbohydrate Polymers, 2023)

High titer (>200 g/L) lactic acid production from undetoxified pretreated corn stover - Yuwei Zhang; Zhaoxian Xu; Minrui Lu; Xingwang Ma; Sitong Chen; Yanchen Wang; Wenyuan Shen; Pingping Li; Mingjie Jin (Bioresource Technology, 2023)

Identification of candidate genes related to two economic traits using GWAS in Gracilariopsis lemaneiformis (Rhodophyta) - Xiaoqing Feng; Baoheng Xiao; Min Jiang; Pingping Li; Qiong Wu; Yingtang Dong; Jiaxing Wang; Zhenghong Sui (Algal Research, 2023)

Hyperspectral images classification of small sample based on the strategy of sample enlargement by superpixel pair method - Xueying Li; Pingping Fan; Zongmin Li; Huimin Qiu; Guangli Hou; Guangyuan Chen; Guoxing Ren (International Journal of Remote Sensing, 2023)

Microplastic aging alters the adsorption-desorption behaviors of sulfamethoxazole in marine animals: A study in simulated biological liquids - Jiaxuan Li; Yunxue Li; Bushra Maryam; Xiaochen Chen; Yanping Zong; Jianbo Tu; Pingping Zhang; Xianhua Liu (Marine Pollution Bulletin, 2023)

Dynamic simulation and control strategy exploration of the unsafe behavior of coal mine employees - Wanzhen Li; Lujie Zhou; Jian Hao; Kai Yu; Jing Chen; Pingping Liu; Rui Feng (Resources Policy, 2023)

Novel TFC membrane with PMIA thin-film as active layer fabricated by the T-FLO technique for dye desalination - Pingping Li; Zhenliang Xu; Dibakar Pandaya; Yinxin Fang; Linglin Gao; Rui Ding; Kaiqi Yu (Journal of Environmental Chemical Engineering, 2023)

Fortification of surimi gels by tuning the synergetic effect of multiple enzyme-related factors - Yadong Zhao; Jiajia Li; Ganping Wei; Xiaoguo Ying; Bin Zheng; Pingping Gao; Rusen Zhou (Food Hydrocolloids, 2023)

Developing of CuxSnSO@GO aerogels used as highly efficient catalysts for cellulose transform to lactic acid under the synergy of Cu-Sn thermocatalysis and photocatalysis processes - Shaocong Yang; Zhen Wang; Pingping Li; Xinrui Wang; Liangyu Li; Chang Geun Yoo; Guihua Yang; Jiachuan Chen; Gaojin Lyu (Chemical Engineering Journal, 2023)

Incorporating biotic phosphorus-acquisition strategies into soil phosphorus transformation under long-term salinization in a tidal wetland - Tianning Fan; Min Luo; Ji Tan; Dehong Hu; Xin Chen; Jiafang Huang; Shihua Li; Pingping Guo; Ji Chen (CATENA, 2023)

Distribution and Controlling Factors of Dissolved Gaseous Mercury and Reactive Mercury in Seawater Near Yangtze River Estuary - Pingping Yin; Wen Zheng; Yan Wang; Ruhai Liu; Xin He; Haolin Sun; Dou Li (Journal of Ocean University of China, 2023)

Analysis of the evolution of the Yellow River Delta coastline and the response of the tidal current field - Lili Zhang; Hongyuan Shi; Hao Xing; Pingping Li; Pengcheng Ma (Frontiers in Marine Science, 2023)
The coastline of the Yellow River Delta has undergone continual alterations due to both natural forces and human activity. Studying these changes is crucial for promoting economic growth and preserving the region’s ecological balance. Based on imagery captured by the Landsat5 and Landsat8 satellites, this study uses statistical data from the Digital Shoreline Analysis System (DSAS), including Net Shoreline Movement (NSM), End Point Rate (EPR), and Linear Regression Rate (LRR), to analyze the changes in the Yellow River Delta coastline from 2009 to 2019. This being the case, a hydrodynamic model under different shoreline conditions was established using Delft3D to compare and analyze the impact of shoreline changes on the tidal current field. From 2009 to 2019, the coastline in the study area exhibited an average movement distance of 1285m (NSM) and an annual change rate of 127.7m/a (LRR). The average increase in the area of the current estuary was 7.68km 2 /a, while the average decrease in the area of the old estuary was 4.91km 2 /a. Shoreline evolution is primarily influenced by the influx of water and sediment into the ocean. Following the implementation of water and sediment regulation, the existing estuary’s shoreline experienced a rapid initial accumulation of silt, which subsequently decelerated over time. Conversely, the former estuary has consistently undergone erosion. The greater the change in shoreline, the closer to the coast, and the greater the change in the tide. From 2009 to 2019, flow velocity and direction in the Yellow River Delta generally showed a decreasing trend, with changes ranging from 0.34% to 25.94%. The residual flow velocity near the current estuary gradually increased by about 2cm/s, while that near the abandoned old estuary gradually decreased by about 1cm/s, with no significant changes offshore. The sediment transported by the Yellow River is deposited at the current estuary, causing the coastline to move northeastward. In the abandoned estuary, there is erosion, causing the coastline to retreat.

Soil carbon content prediction using multi-source data feature fusion of deep learning based on spectral and hyperspectral images - Xueying Li; Zongmin Li; Huimin Qiu; Guangyuan Chen; Pingping Fan (Chemosphere, 2023)

Bacterial wilt suppressive composts: Significance of rhizosphere microbiome - Jia Ding; Ning Wang; Pingping Liu; Baoju Liu; Yuelin Zhu; Jing Mao; Yue Wang; Xiaoyan Ding; Hefa Yang; Yuquan Wei; Ji Li; Guo-chun Ding (Waste Management, 2023)

Antioxidant and antimicrobial collagen films incorporating Pickering emulsions of cinnamon essential oil for pork preservation - Ruimin Ran; Tingting Zheng; Pingping Tang; Yongming Xiong; Changkai Yang; Min Gu; Guoying Li (Food Chemistry, 2023)

Collagen films functionalized with gallic acid in the presence of laccase for beef preservation - Pingping Tang; Tingting Zheng; Ruimin Ran; Yongming Xiong; Guoying Li (Food Packaging and Shelf Life, 2023)

NIR-II photo-amplified peroxidase-like activity using biocatalytic copper-based nanoplatform against subcutaneous methicillin-resistant Staphylococcus aureus infection - Danyan Wang; Xiaojun He; Qiang Wang; Pingping Li; Enoch Obeng; Dongyang Zheng; Jianliang Shen; Zi Jin (Chemical Engineering Journal, 2023)

Establishment of TRV-mediated Gene Silencing and Application for Elucidating Functions of Anthocyanidin Reductase Gene HcANR in Kenaf (Hibiscus cannabinus L.) - Xin Yang; Hu Li; Sylvain Niyitanga; Lilan Zhang; Xingen Li; Jianmin Qi; Jiantang Xu; Aifen Tao; Pingping Fang; Liwu Zhang (Tropical Plant Biology, 2023)

Shallow plough tillage with straw return increases rice yield by improving nutrient availability and physical properties of compacted subsurface soils - Pingping Wu; Lujiu Li; Xiao Wang (Nutrient Cycling in Agroecosystems, 2023)

Highly sensitive detection of microRNA-21 by nitrogen-doped carbon dots-based ratio fluorescent probe via nuclease-assisted rolling circle amplification strategy - Shan Huang; Bo Li; Pingping Mu; Wenqian Zhang; Yi Liu; Qi Xiao (Analytica Chimica Acta, 2023)

Above management: Scale development and empirical testing for public opinion monitoring of marine pollution - Jihong Chen; Pingping Li; Xue Wang; Kui Yi (Marine Pollution Bulletin, 2023)

Structural and functional diversity of the microbiome during the Phaeocystis globosa winter bloom in the southern Yellow Sea of China - Yue Xue; Qingshang Song; Dongmei Li; Xiyan Wang; Hui Liu; Cunchao Wu; Pingping Shen (International Biodeterioration & Biodegradation, 2023)

Development of active packaging films based on collagen/gallic acid-grafted chitosan incorporating with ε-polylysine for pork preservation - Tingting Zheng; Pingping Tang; Changkai Yang; Ruimin Ran; Guoying Li (Food Hydrocolloids, 2023)

Immunomodulatory Mechanisms and Therapeutic Potential of Mesenchymal Stem Cells - Guoqiang Yang; Xuehui Fan; Yingchun Liu; Pingping Jie; Maryam Mazhar; Yong Liu; Nathupakorn Dechsupa; Li Wang (Stem Cell Reviews and Reports, 2023)
Mesenchymal stem cells (MSCs) are regarded as highly promising cells for allogeneic cell therapy, owing to their multipotent nature and ability to display potent and varied functions in different diseases. The functions of MSCs, including native immunomodulation, high self-renewal characteristic, and secretory and trophic properties, can be employed to improve the immune-modulatory functions in diseases. MSCs impact most immune cells by directly contacting and/or secreting positive microenvironmental factors to influence them. Previous studies have reported that the immunomodulatory role of MSCs is basically dependent on their secretion ability from MSCs. This review discusses the immunomodulatory capabilities of MSCs and the promising strategies to successfully improve the potential utilization of MSCs in clinical research. Graphical Abstract

Factors inducing morphological transition in harmful algal bloom-forming species Phaeocystis globosa with emphasis on predator chemical cue - Xiao Yang; Pingping Shen; Ke Li (Journal of Oceanology and Limnology, 2023)

Evaluation of cigarette smoke-induced oxidative stress and inflammation in BEAS-2B cells based on a lung microfluidic chip - Jingxian Xue; Zezhi Li; Xiang Li; Chenfeng Hua; Pingping Shang; Junwei Zhao; Kejian Liu; Fuwei Xie (Food and Chemical Toxicology, 2023)

Numerical Simulation of the Beach Response Mechanism under Typhoon Lekima: A Case Study of the Southern Beach of Chudao - Hao Xing; Pingping Li; Lili Zhang; Huaiyuan Xue; Hongyuan Shi; Zaijin You (Journal of Marine Science and Engineering, 2023)
Typhoons play an important role in beach evolution. The storm surge and large waves caused by typhoons can cause significant changes in beach morphology in a short period of time. The mechanism of beach evolution and profile changes during typhoons is significantly different from that under non-typhoon dynamic conditions. The XBeach numerical model provides an effective tool for predicting the response of sandy coasts to typhoons. This study is based on field-collected long-term beach profile elevations and grain size data, which were used to establish a two-dimensional XBeach model for simulating the morphological evolution of Cudao Island Beach under Typhoon Lekima. The GSA (Generalized Sensitivity Analysis) method was used to determine the sensitivity order of several important parameters in this modeling. Four different moments of wave height variation were selected during the typhoon process to analyze and study beach evolution. The results show that Chudao South Beach is always in a state of erosion during the typhoon period. The wave water increase is apparent in the nearshore wave-breaking area. The beach shoulder in the northeastern part of the beach is short, and the profile, with a short length, responds quickly to the typhoon. The eroded sediment is mainly deposited in the lower part of the intertidal zone or even transported outside of the wave-breaking zone, and a small part is transported to the shore and deposited in the high-tide zone. The continuous sediment transport along the coast of Chudao Beach is an important factor that influenced the evolution of each profile during Typhoon Lekima.

Secukinumab plays a synergistic role with starvation therapy in promoting autophagic cell death of hepatocellular carcinoma via inhibiting IL-17A-increased BCL2 level - Rong Tang; Linmei Zheng; Jinfang Zheng; Jincai Wu; Pingping Chen; Jiacheng Chen; Dafeng Xu; Yongchao Zeng; Qijin Li; Zhensheng Zhang (In Vitro Cellular & Developmental Biology - Animal, 2023)

Polycyclic aromatic hydrocarbons in the Chinese diet: contamination characteristics, indicator screening, and health risk assessment - Feifei Huang; Lei Zhang; Moqin Zhou; Jianwen Li; Qing Liu; Bo Wang; Ke Deng; Pingping Zhou; Yongning Wu (Food Additives & Contaminants: Part A, 2023)

Effects of heavy rain on the concentrations and forms of carbon, nitrogen and phosphorus in urban rivers of northern China - Wenchao Li; Jiehua Wang; Yunkai Zhou; Pingping Zhang; Xiuling Bai (Environmental Science and Pollution Research, 2023)

Depositional processes of the mixed siliciclastic-carbonate system in the Lower Cambrian Xiannüdong Formation in the northern Sichuan Basin, South China - Ting Li; Weiqiang Yang; Chaojin Lu; Pingping Li; Zhehang Xu; Yuan He; Jinbao Duan; Huayao Zou (Marine and Petroleum Geology, 2023)

Integration of nitrogen-doped carbon dots onto active layer of forward osmosis membrane for highly efficient antibacteria and enhanced membrane performances - Wen-Sheng Zou; Pingping Wu; Bihua Xiao; Xia Chen; Weili Kong; Yaru Li; Zhaoming Liu; Yaqin Wang (Journal of Environmental Chemical Engineering, 2023)

Antibacterial castor oil-based waterborne polyurethane/gelatin films for packaging of strawberries - Yuye Zhong; Tao Zhang; Wenshuo Zhang; Guannan Wang; Zhenhong Zhang; Pingping Zhao; Xinghai Liu; Houbin Li (Food Packaging and Shelf Life, 2023)

High-titer production of myo-inositol by a co-immobilized four-enzyme cocktail in biomimetic mineralized microcapsules - Pingping Han; Chun You; Yunjie Li; Ting Shi; Hong Wu; Yi-Heng P. Job Zhang (Chemical Engineering Journal, 2023)

TaLBD1, a LOB transcription factor gene in T. aestivum, confers plant adaptation to low-N stress via modulating N acquisition-associated processes - Yanyang Zhang; Chenyang Ni; Tianjiao Li; Le Han; Pingping Du; Kai Xiao (Plant Cell, Tissue and Organ Culture (PCTOC), 2023)

Carbon amendment rather than nitrate fertilization dominated the reassembly of the total, denitrifying, and DNRA bacterial community in the anaerobic subsoil - Chen Chen; Pingping Liu; Yingjie Liu; Yuquan Wei; Ji Li; Guo-chun Ding (Journal of Soils and Sediments, 2023)

Changes in bacterial diversity, co-occurrence pattern, and potential pathogens following digestate fertilization: Extending pathogen management to field for anaerobic digestion of livestock manure - Jingyang Gong; Baojun Liu; Pingping Liu; Lina Zhang; Chen Chen; Yuquan Wei; Ji Li; Guo-chun Ding (Waste Management, 2023)

Insights into carbon loss reduction during aerobic composting of organic solid waste: A meta-analysis and comprehensive literature review - Pingping Ye; Linfa Fang; Dan Song; Muyuan Zhang; Ronghua Li; Mukesh Kumar Awasthi; Zengqiang Zhang; Ran Xiao; Xinping Chen (Science of The Total Environment, 2023)

EST-SSR development and genetic diversity in the medicinal plant Pseudostellaria heterophylla (Miq.) Pax - Liyi Xu; Pingping Li; Jingjing Su; Ding Wang; Yunbo Kuang; Zuyun Ye; Meixia Chen (Journal of Applied Research on Medicinal and Aromatic Plants, 2023)

Comparison between diffusive gradients in thin film technology (DGT) and traditional methods for prediction of plant available heavy metals in agricultural soil - Xiuling Bai; Wenna Ye; Yunkai Zhou; Xinling Ruan; Jiehua Wang; Wenchao Li; Pingping Zhang (Journal of Soils and Sediments, 2023)

The PER3rs772027021 SNP induces pigmentation phenotypes of dyschromatosis universalis hereditaria - Hongyu Chen; Pingping Yang; Dan Yang; Dongsheng Wang; Mao Lu; Yadong Li; Zhiqiang Zhong; Jing Zhang; Zhen Zeng; Zhi Liu; Xiaohua Zeng; Xu Jia; et al. (Journal of Molecular Medicine, 2023)

Speciation and source changes of atmospheric arsenic in Qingdao from 2016 to 2020 - Response to control policies in China - Haolin Sun; Yan Wang; Ruhai Liu; Pingping Yin; Dou Li; Long Shao (Chemosphere, 2023)

Spatial-temporal heterogeneity analysis of blue and green water resources for Poyang Lake basin, China - Mengyuan Liu; Pingping Zhang; Yanpeng Cai; Jianwen Chu; Yunliang Li; Xuan Wang; Chunhui Li; Qiang Liu (Journal of Hydrology, 2023)

Development of a pH-sensitive film based on collagen/chitosan/ZnO nanoparticles and mulberry extract for pork freshness monitoring - Tingting Zheng; Pingping Tang; Guoying Li (Food Chemistry, 2023)

HADHA alleviates hepatic steatosis and oxidative stress in NAFLD via inactivation of the MKK3/MAPK pathway - Jiexia Ding; Lili Wu; Guoxian Zhu; Jing Zhu; Pingping Luo; Youming Li (Molecular Biology Reports, 2023)
Background Nonalcoholic fatty liver disease (NAFLD) is a liver metabolic syndrome and still lacks effective treatments because the molecular mechanism underlying the development of NAFLD is not completely understood. We investigated the role of Hydroxyl CoA dehydrogenase alpha subunit (HADHA) in the pathogenesis of NAFLD. Methods HADHA expression was detected both in NAFLD cell and mice, and knockdown of HADHA in free fatty acids (FFA)-treated L02 or overexpression of HADHA in high fat diet (HFD)-fed mice was used to detected the influence of HADHA on hepatic steatosis, mitochondrial dysfunction, and oxidative stress by regulating of MKK3/MAPK signaling. Results Our data revealed that HADHA expression was decreased in FFA-treated L02 cells and in HFD-fed mice. Knockdown of HADHA markedly aggravated hepatic steatosis, inflammation and oxidative stress in FFA-treated L02 cells, which was associated with the activation of MKK3/MAPK signalling pathways. Moreover, oxidative stress and liver lesions were improved in NAFLD mice by upregulation of HADHA. Importantly, we demonstrated that overexpression of HADHA inhibited the expression of p-MAPK in NAFLD mice, reducing lipid accumulation and steatosis. Conclusion HADHA may function as a protective factor in the progression of NAFLD by alleviating abnormal metabolism and oxidative stress by suppressing MKK3/MAPK signalling pathway activation, providing a new target for the treatment of NAFLD.

Identification of methyl 1-aminocyclopropanecarboxylate as a novel ethylene agonist: a structural analogy approach - Xiaofang Li; Pingping Fang; Mingxuan Li; Pei Xu (In Vitro Cellular & Developmental Biology - Plant, 2023)

Effects of nutrient deficiency on the branch phenotype of the macroalgae Gracilariopsis lemaneiformis (Rhodophyta) - Pingping Li; Haihong Chen; Jingyu Zhang; Xiaoqing Feng; Baoheng Xiao; Yiyi Hu; Zhenghong Sui (Aquaculture, 2023)

Cytotoxicity and pro-inflammatory effect of polystyrene nano-plastic and micro-plastic on RAW264.7 cells - Xiaoxia Wang; Xiao-Min Ren; Huan He; Fan Li; Kunqian Liu; Fenqing Zhao; Huixiang Hu; Pingping Zhang; Bin Huang; Xuejun Pan (Toxicology, 2023)

Transcription factor NtWRKY33a modulates the biosynthesis of polyphenols by targeting NtMYB4 and NtHCT genes in tobacco - Zhong Wang; Lanxin Ma; Pingping Liu; Zhaopeng Luo; Zefeng Li; Mingzhu Wu; Xin Xu; Wenxuan Pu; Pingjun Huang; Jun Yang (Plant Science, 2023)

Metagenomic insights into the changes in the rhizosphere microbial community caused by the root-knot nematode Meloidogyne incognita in tobacco - Peng Lu; Heli Shi; Jiemeng Tao; Jingjing Jin; Sujie Wang; Qingxia Zheng; Pingping Liu; Bikun Xiang; Qiansi Chen; Yalong Xu; Zefeng Li; Jun Tan; et al. (Environmental Research, 2023)

What happens to gut microorganisms and potential repair mechanisms when meet heavy metal(loid)s - Xiaoyi Liu; Jinhua Zhang; Jing Si; Pingping Li; Haining Gao; Weikun Li; Yong Chen (Environmental Pollution, 2023)

K+ and CeO2 nanoparticles modified OMS-2 nanorods for enhanced activity and stability of photocatalytic toluene oxidation: K+ charge modulation and mechanistic investigation - Pingping Yu; Nan Li; Weixin Zou; Xiaoqian Wei; Jiawei Ji; Li Han; Yandi Cai; Wei Tan; Bin Gao; Lin Dong (Chemical Engineering Journal, 2023)

Application of an integrated loach-plant-substrate-microbes non-aerated saturated vertical flow constructed wetlands: Mechanisms of pollutants removal and greenhouse gases reduction - Xiuzheng Fu; Zhengda Yu; Fanlong Kong; Pingping Duan; Fanyi Li; Lingzhu Zhang; Zhongying Liu; Yuqian Cui (Bioresource Technology, 2023)

Aquaculture Exacerbates the Accumulation and Ecological Risk of Heavy Metal from Anthropogenic and Natural Sources, a Case Study in Hung-tse Lake, China - Jiping Li; Hao Cui; Yanhui Guo; Pingping Li; Jiangang Han; Wei Li (Water, Air, & Soil Pollution, 2023)

Transcriptomes of Different Tissues for Expression Characteristics Analysis of MYB gene Family in Kenaf (Hibiscus cannabinus L.) - Hu Li; Xin Yang; Sylvain Niyitanga; Qinyao He; Siyuan Chen; Jiantang Xu; Jianmin Qi; Aifen Tao; Pingping Fang; Liwu Zhang (Tropical Plant Biology, 2022)

Expression of RUNX2/LAPTM5 in the Induction of MC3T3-e1 Mineralization and Its Possible Relationship with Autophagy - Lei Xing; Yanqin Li; Wenhao Li; Rong Liu; Yuanming Geng; Weiqun Ma; Yu Qiao; Jianwen Li; Yingtao Lv; Ying Fang; Pingping Xu (Tissue Engineering and Regenerative Medicine, 2022)

Development and Application of Three-Dimensional Bioprinting Scaffold in the Repair of Spinal Cord Injury - Dezhi Lu; Yang Yang; Pingping Zhang; Zhenjiang Ma; Wentao Li; Yan Song; Haiyang Feng; Wenqiang Yu; Fuchao Ren; Tao Li; Hong Zeng; Jinwu Wang (Tissue Engineering and Regenerative Medicine, 2022)

Ploidy Identification by Flow Cytometry and Application of the Method to Characterize Seasonal Ploidy Variation of Wild Populations of the Red Alga Gracilariopsis lemaneiformis - Xiaoqing Feng; Haihong Chen; Baoheng Xiao; Qiong Wu; Jingyu Zhang; Ni Zhang; Pingping Li; Lu Wang; Jingru Yin; Zhenghong Sui (Marine Biotechnology, 2022)

Application of resistivity measurement to stability evaluation for loess slopes - Bin Zhang; Li Feng; Maosheng Zhang; Pingping Sun; Tonglu Li; Hao Liu (Landslides, 2022)

Comparative transcriptome analysis unravels the response mechanisms of Cytospora mali QH2 to a biocontrol agent, Bacillus velezensis L-1 - Pingping Sun; Lei Zhang; Zhengnan Li (European Journal of Plant Pathology, 2022)

Identification and Characterization of microRNAs in the Gonads of Litopenaeus vannamei Using High-Throughput Sequencing - Wei Li; Pingping He; Xingzhi Zhang; Junliang Guan; Yongxian Chen; Li Zhang; Bin Zhang; Yusi Zheng; Xin Li; Qingsong He; Longcheng Liu; Chang Yuan; et al. (Fishes, 2022)
Although the expression of miRNAs has been widely applied to investigate on gonads, the role of miRNAs in the gonadal development of white Pacific shrimp (Litopenaeus vannamei) remains unknown. In this study, we performed high-throughput sequencing to identify the sex-related microRNAs (miRNAs) that elucidated the regulatory mechanisms on the gonadal differentiation of L. vannamei. We obtained a total of 29,671,557 and 28,526,942 raw reads from the ovaries and testes library, respectively. We then mapped 26,365,828 (92.73%) of the ovarian clean sequences and 23,694,294 (85.65%) of the testicular clean sequences for a transcriptome reference sequence of L. vannamei. After blasting the miRNA sequences against the miRBase database, we identified 153 significantly differentially expressed miRNAs between the ovaries and testes. To confirm the high-throughput sequencing results, we used a reverse transcriptase–quantitative polymerase chain reaction (RT-qPCR) to verify the expression patterns of the seven most differentially expressed miRNAs (i.e., novel_mir23, miR-92b-3p_3, miR-12-5p_2, novel_mir67, miR-279_1, let-7-5p_6, miR-263a-5p_1). According to the results of RT-qPCR, most of the miRNAs were expressed consistently with the high-throughput sequencing results. In addition, the target genes significantly enriched several Kyoto Encyclopedia of Genes and Genome (KEGG) pathways that were closely related to gonadal differentiation and development, including extracellular matrix–receptor interaction, Hedgehog signaling pathway, protein digestion and absorption and cell adhesion molecules (CAMs). This study revealed the first miRNAs sequencing of L. vannamei gonads. We identified sex-related differentially expressed miRNAs and KEGG pathways, which will be helpful to facilitate future research into the regulatory mechanism on the gonadal differentiation of L. vannamei.

Cellular Heterogeneity Facilitates the Functional Differences Between Hair Follicle Dermal Sheath Cells and Dermal Papilla Cells: A New Classification System for Mesenchymal Cells within the Hair Follicle Niche - Yuyang Gan; Hailin Wang; Lijuan Du; Kaitao Li; Qian Qu; Weiwen Liu; Pingping Sun; Zhexiang Fan; Jin Wang; Ruosi Chen; Zhiqi Hu; Yong Miao (Stem Cell Reviews and Reports, 2022)

Breast Cancer Awareness Based on Health Information Literacy and Influential Factors among Female Nursing Students in China - Shu Yang; Ping Li; Lin Yu; Na Liu; Jie Wang; Pingping Guo; Xuehui Zhang; Wei Zhang (Journal of Cancer Education, 2022)

Analysis and Model Comparison of Carbon and Nitrogen Concentrations in Sediments of the Yellow Sea and Bohai Sea by Visible-Near Infrared Spectroscopy - Huimin Qiu; Pingping Fan; Guangli Hou; Xueying Li; Yinglong Wang (Bulletin of Environmental Contamination and Toxicology, 2022)

Complete genomic characterization of a reassortment isolate of Sophora yellow stunt virus from Sophora alopecuroides in China - Shuang Song; Pingping Sun; Mingxiu Ju; Xuan Zhang; Xingqi Yang; Lei Zhang; Zhengnan Li (Journal of Plant Pathology, 2022)

Dexmedetomidine post-conditioning alleviates myocardial ischemia–reperfusion injury in rats by ferroptosis inhibition via SLC7A11/GPX4 axis activation - Peng Yu; Jing Zhang; Yi Ding; Dandan Chen; Haijian Sun; Fenglai Yuan; Siyuan Li; Xiaozhong Li; Pingping Yang; Linghua Fu; Shuchun Yu; Jiru Zhang (Human Cell, 2022)

First Report on Large-Scale Phaeocystis globosa Bloom in the Southern Yellow Sea, China - Dongmei Li; Yue Xue; Qingshang Song; Fuxu Cui; Yujuan Ma; Mengmeng Tong; Pingping Shen (Frontiers in Marine Science, 2022)
From late November 2021, a large-scale Phaeocystis globosa bloom occurred for the first time in the southern Yellow Sea, covering an area of over 630 km 2 and lasting for nearly 40 days. Two investigations, combined with satellite remote sensing, were successively conducted on December 11 and 23, 2021 to study the bloom dynamics and impacts. During the bloom, the average temperature decreased from 11.8°C to 10.0°C and salinity increased slightly from 30.9 to 31.3. The pH remained consistently at 8.22, while dissolved oxygen and chlorophyll -a content decreased dramatically from 7.23 mg L -1 to 5.82 mg L -1 , 8.72 μg L -1 to 2.35 μg L -1 , respectively. The concentration of nitrate and silicate decreased moderately, whereas nitrite, ammonium and phosphate increased obviously, especially the ammonium content, elevated from 0.90 μmol L -1 to 1.39 μmol L -1 during two investigations. Meanwhile, the P. globosa colony densities varied between 10 colonies L -1 and 185 colonies L -1 , with a mean of 70.0 colonies L -1 on Dec. 11, and decreased dramatically to an average of 1.46 colonies L -1 on Dec. 23. Similarly, single cells decreased from 3.6×10 6 cells L -1 to 1.05×10 6 cells L -1 accordingly. Moreover, diameter of the colonies varied from 0.5 cm to 2.0 cm, with an average diameter of 1.0 cm, and no colonies smaller than 0.5 cm was observed in the bloom. Correlation analysis indicated temperature and salinity related with the colony abundance positively (P<0.001) and negatively (P<0.05), respectively, and silicate and nitrite concentration showed significant positive effects on solitary cell density (P<0.05). No mortality of marine organisms was observed and the haemolytic activity of Phaeocystis samples was low, varying between 13.07 Hu L -1 and 19.22 Hu L -1 . Based on phylogenetic analysis, this P. globosa strain may represent a possible different ecotype which prefers low temperature and is less or nontoxicity.

Mutant library resources for legume crops and the emerging new screening technologies - Wenjun Xia; Peipei Zhang; Xinyang Wu; Mingxuan Li; Ting Sun; Pingping Fang; Arun K. Pandey; Pei Xu (Euphytica, 2022)

Induction and Genomic Analysis of a Lysogenic Phage of Hafnia paralvei - Lingting Pan; Dengfeng Li; Yigang Tong; Wei Lin; Weinan Qin; Lihua Xu; Pingping Zhan (Current Microbiology, 2022)

Dysregulated lncRNA and mRNA may promote the progression of ischemic stroke via immune and inflammatory pathways: results from RNA sequencing and bioinformatics analysis - Yingshuang Wang; Feifei Feng; Pingping Zheng; Lijuan Wang; Yanjun Wang; Yaogai Lv; Li Shen; Kexin Li; Tianyu Feng; Yang Chen; Zhigang Liu; Yan Yao (Genes & Genomics, 2022)

Identification of MicroRNAs as potential biomarkers for detecting ischemic stroke - Kexin Li; Li Shen; Pingping Zheng; Yanjun Wang; Lijuan Wang; Xiaoli Meng; Yaogai Lv; Zhiqiang Xue; Xin Guo; Anning Zhang; Pan Pan; Chunli Bi; et al. (Genes & Genomics, 2022)

Spatial and temporal variation of dissolved heavy metals in the Lijiang River, China: implication of rainstorm on drinking water quality - Liming Deng; Asfandyar Shahab; He Xiao; Jieyue Li; Saeed Rad; Jinping Jiang; GuoYu; Pingping Jiang; Hongwei Huang; Xiangkui Li; Bilal Ahmad; Jamil Siddique (Environmental Science and Pollution Research, 2021)

Assessing the environmental impact of China’s tourism activities: a tourism heat footprint method - Shuxin Wang; Weihong Cao; Jiankuo Du; Pingping Tang; Hengyang Fu; Zi Tang; Jiamei Li (Environmental Science and Pollution Research, 2021)

Prenatal diagnosis of the Dandy–Walker malformation associated with partial trisomy 12p and distal 15q deletion - Yanmei Sun; Ning Zhang; Haishen Tian; Pingping Zhang; Yali Li (Journal of Genetics, 2021)

Transcriptional Responses of Flavin-Containing Monooxygenase Genes in Scallops Exposed to PST-Producing Dinoflagellates Implying Their Involvements in Detoxification - Lingling Kong; Pingping Liu; Moli Li; Huizhen Wang; Jiaoxia Shi; Jingjie Hu; Yueru Li; Xiaoli Hu (Frontiers in Marine Science, 2021)
Flavin-containing monooxygenase (FMO) is one of the most prominent xenobiotic metabolic enzymes. It can catalyze the conversion of heteroatom-containing chemicals to polar, readily excretable metabolites and is considered an efficient detoxification system for xenobiotics. Bivalves can accumulate paralytic shellfish toxins (PSTs) produced by dinoflagellates, especially during outbreaks of harmful algal blooms. Exploring FMO genes in bivalves may contribute to a better understanding of the adaptation of these species and the mechanisms of PSTs bioavailability. Therefore, through genome screening, we examined the expansion of FMO genes in two scallops ( Patinopecten yessoensis and Chlamys farreri ) and found a new subfamily (FMO_like). Our expression analyses revealed that, in both scallops, members of the FMO_N-oxide and FMO_like subfamilies were mainly expressed from the D-stage larvae to juveniles, whereas the FMO_GS-OX subfamily genes were mainly expressed at and prior to the trochophore stage. In adult organs, higher expressions of FMO s were observed in the kidney and hepatopancreas than in other organs. After exposure to PST-producing algae, expression changes in FMO s occurred in hepatopancreas and kidney of both scallops, with more members being up-regulated in hepatopancreas than in kidney for Alexandrium catenella exposure, while more up-regulated FMO s were found in kidney than in hepatopancreas of C. farreri exposed to A. minutum . Our findings suggest the adaptive functional diversity of scallop FMO genes in coping with the toxicity of PST-producing algae.

Occurrence of 3- and 2-monochloropropanediol esters in infant formulas in China and exposure assessment - Xia Cui; Lei Zhang; Dajin Yang; Jianwen Li; Qing Liu; Haixia Sui; Zhaoping Liu; Pingping Zhou (Food Additives & Contaminants: Part A, 2021)

rno-miR-128-3p promotes apoptosis in rat granulosa cells (GCs) induced by norepinephrine through Wilms tumor 1 (WT1) - Ming Li; Ling Xue; Weibin Xu; Pingping Liu; Feng Li (In Vitro Cellular & Developmental Biology - Animal, 2021)
The mechanism related to ovarian follicular is complex, which has not been fully elucidated. Abundant reports have confirmed that the ovarian function development is closely related to sympathetic innervation. As one of the major neurotransmitters, norepinephrine (NE) is considered an effective regulator of ovarian functions like granulosa cell (GC) apoptosis. However, the mechanism between NE and GC apoptosis in rat is still unclear. In our study, GCs were isolated and cultured in vitro with NE treatment. The apoptosis of GCs was facilitated by NE. Wilms tumor 1 (WT1) was found to be significantly downregulated in GCs after NE treatment, and overexpression of WT1 repressed apoptosis in rat GCs induced by NE. rno-miR-128-3p was found to be significantly enhanced by NE in GCs, and inhibition of rno-miR-128-3p repressed apoptosis in rat GCs induced by NE. Mechanistically, rno-miR-128-3p interacted with WT1 and repressed its expression. In summary, inhibition of rno-miR-128-3p may enhance WT1 expression, and then repress NE-induced apoptosis in rat GCs. Our research may provide a new insight for the improvement of ovarian follicular development.

LncRNA Neat1 Promotes Regeneration after Spinal Cord Injury by Targeting miR-29b - Guangtao Bai; Liang Jiang; Pingping Meng; Jiang Li; Chao Han; Yuyang Wang; Qiang Wang (Journal of Molecular Neuroscience, 2021)

Causal associations of waist circumference and waist-to-hip ratio with type II diabetes mellitus: new evidence from Mendelian randomization - Kexin Li; Tianyu Feng; Lijuan Wang; Yang Chen; Pingping Zheng; Pan Pan; Min Wang; Isaac T. S. Binnay; Yingshuang Wang; Ruiyu Chai; Siyu Liu; Bo Li; et al. (Molecular Genetics and Genomics, 2021)

Development and evaluation of a serological test for diagnosis of COVID-19 with selected recombinant spike proteins - Pingping Zhang; Qi Gao; Tang Wang; Yuehua Ke; Fei Mo; Ruizhong Jia; Wanbing Liu; Lei Liu; Shangen Zheng; Yuzhen Liu; Luping Li; Yao Wang; et al. (European Journal of Clinical Microbiology & Infectious Diseases, 2021)

Characterization on the physiological traits of plants and yield formation capacity upon water- and N-saving conditions in wheat (T. aestivum L.) - Pingping Du; Liguo Guo; Lili Si; Le Han; Shuang Zhang; Fangfang Li; Kai Xiao (Acta Physiologiae Plantarum, 2021)

Occurrence and molecular variability of apple-associated Luteovirus isolates from apple in China based on coat protein genes - Zhengnan Li; Mingxiu Ju; Lei Zhang; Mengji Cao; Pingping Sun (European Journal of Plant Pathology, 2021)

Use of multiple isotopes to evaluate nitrate dynamics in groundwater under the barrier effect of underground cutoff walls - Pingping Kang; Shaopeng Li; Fuqiang Wang; Heng Zhao; Subing Lv (Environmental Science and Pollution Research, 2021)

Development and application of a comparative risk assessment method for ranking chemical hazards in food - Ying Li; Guoxin Liang; Lei Zhang; Zhaoping Liu; Dajin Yang; Jianwen Li; Guiju Sun; Pingping Zhou (Food Additives & Contaminants: Part A, 2021)

Dietary exposure of general Chinese population to fatty acid esters of 3-monochloropropane-1, 2-diol (3-MCPD) from edible oils and oil-containing foods - Xia Cui; Lei Zhang; Pingping Zhou; Zhaoping Liu; Sai Fan; Dajin Yang; Jianwen Li; Qing Liu (Food Additives & Contaminants: Part A, 2021)

Characterization of Anchorless Human PrP With Q227X Stop Mutation Linked to Gerstmann-Sträussler-Scheinker Syndrome In Vivo and In Vitro - Pingping Shen; Johnny Dang; Zerui Wang; Weiguanliu Zhang; Jue Yuan; Yue Lang; Mingxuan Ding; Marcus Mitchell; Qingzhong Kong; Jiachun Feng; Annemiek J. M. Rozemuller; Li Cui; et al. (Molecular Neurobiology, 2021)
Alteration in cellular prion protein (PrP C ) localization on the cell surface through mediation of the glycosylphosphatidylinositol (GPI) anchor has been reported to dramatically affect the formation and infectivity of its pathological isoform (PrP Sc ). A patient with Gerstmann-Sträussler-Scheinker (GSS) syndrome was previously found to have a nonsense heterozygous PrP-Q227X mutation resulting in an anchorless PrP. However, the allelic origin of this anchorless PrP Sc and cellular trafficking of PrP Q227X remain to be determined. Here, we show that PrP Sc in the brain of this GSS patient is mainly composed of the mutant but not wild-type PrP (PrP Wt ), suggesting pathological PrP Q227X is incapable of recruiting PrP Wt in vivo. This mutant anchorless protein, however, is able to recruit PrP Wt from humanized transgenic mouse brain but not from autopsied human brain homogenates to produce a protease-resistant PrP Sc -like form in vitro by protein misfolding cyclic amplification (PMCA). To further investigate the characteristics of this mutation, constructs expressing human PrP Q227X or PrP Wt were transfected into neuroblastoma cells (M17). Fractionation of the M17 cells demonstrated that most PrP Wt is recovered in the cell lysate fraction, while most of the mutant PrP Q227X is recovered in the medium fraction, consistent with the results obtained by immunofluorescence microscopy. Two-dimensional gel-electrophoresis and Western blotting showed that cellular PrP Q227X spots clustered at molecular weights of 22–25 kDa with an isoelectric point ( p I) of 3.5–5.5, whereas protein spots from the medium are at 18–26 kDa with a p I of 7–10. Our findings suggest that the role of GPI anchor in prion propagation between the anchorless mutant PrP and wild-type PrP relies on the cellular distribution of the protein.

The origin of arc basalts: New advances and remaining questions - Yigang Xu; Qiang Wang; Gongjian Tang; Jun Wang; Hongyan Li; Jinsheng Zhou; Qiwei Li; Yue Qi; Pingping Liu; Lin Ma; Jingjing Fan (Science China Earth Sciences, 2020)

Culturally Tailored Intervention to Promote Mammography Screening Practice Among Chinese American Women: a Systematic Review - Xuehui Zhang; Ping Li; Pingping Guo; Jie Wang; Na Liu; Shu Yang; Lin Yu; Xiumin Zhang; Wei Zhang (Journal of Cancer Education, 2020)

PD-1 expression is elevated in monocytes from hepatocellular carcinoma patients and contributes to CD8 T cell suppression - Jin Yun; Genhua Yu; Pingping Hu; Yang Chao; Xingyu Li; Xiaobo Chen; Qichun Wei; Junfeng Wang (Immunologic Research, 2020)

Prenatal diagnosis and neonatal phenotype of a de novo microdeletion of 17p11.2p12 associated with Smith‒Magenis syndrome and external genital defects - Pingping Zhang; Yanmei Sun; Haishen Tian; Limin Rong; Fangna Wang; Xiaoping Yu; Yali Li; Jian Gao (Journal of Genetics, 2020)

Benzophenanthridine alkaloids suppress lung adenocarcinoma by blocking TMEM16A Ca2+-activated Cl− channels - Gaohua Zhang; Lin Zhu; Yucong Xue; Zhijun Zhao; Honglin Li; Zhiyun Niu; Xiangchong Wang; Pingping Chen; Jianping Zhang; Xuan Zhang (Pflügers Archiv - European Journal of Physiology, 2020)

Mechano growth factor pretreatment yield mechanical stimuli induced cell stress responses in ligament fibroblasts of osteoarthritis via activating ATF-2 - Yu Ma; Yang Song; Linhao Li; Lili Dong; Chunli Wang; Pingping Wang; Li Yang (Biotechnology Letters, 2020)

Depositional environments of limestones from the Taiyuan Formation in the North China Block interpreted from REE proxies - Dawei Lv; Wengui Fan; John I. Ejembi; Dun Wu; Dongdong Wang; Zengxue Li; Junpeng Li; Pingping Li (Carbonates and Evaporites, 2020)

Alcohol inhibits morphine/cocaine reward memory acquisition and reconsolidation in rats - Shimin Zhu; Pingping Chen; Mingzhu Chen; Jiawei Ruan; Wanying Ren; Xinyu Zhang; Yang Gao; Yanqin Li (Psychopharmacology, 2020)

An effective method for identification of three mussel species and their hybrids based on SNPs - Xingqiang Chen; Ronghua Li; Chunlin Wang; Changkao Mu; Weiwei Song; Lei Liu; Ce Shi; Pingping Zhan (Conservation Genetics Resources, 2020)

Molecular identification reveals hybrids of Mytilus coruscus × Mytilus galloprovincialis in mussel hatcheries of China - Weijia Zhang; Ronghua Li; Xingqiang Chen; Chunlin Wang; Zhongqi Gu; Changkao Mu; Weiwei Song; Pingping Zhan; Ji Huang (Aquaculture International, 2020)

Glutamate and aspartate alleviate testicular/epididymal oxidative stress by supporting antioxidant enzymes and immune defense systems in boars - Wenjie Tang; Jian Wu; Shunshun Jin; Liuqin He; Qinlu Lin; Feijun Luo; Xingguo He; Yanzhong Feng; Binsheng He; Pingping Bing; Tiejun Li; Yulong Yin (Science China Life Sciences, 2020)

Risk grade assessment of sudden water pollution based on analytic hierarchy process and fuzzy comprehensive evaluation - Hao Zhang; Wenjun Li; Pingping Miao; Bowen Sun; Fanqing Kong (Environmental Science and Pollution Research, 2020)

Reactive oxygen species induced by personal exposure to fine particulate matter emitted from solid fuel combustion in rural Guanzhong Basin, northwestern China - Yaqi Li; Hongmei Xu; Kailai He; Jinhui Wang; Zhi Ning; Qiyuan Wang; Nan Li; Zhenxing Shen; Pingping Liu; Jian Sun; Xinyi Niu; Yongxiao Cao; et al. (Air Quality, Atmosphere & Health, 2019)

Early Cretaceous volcanic and sub-volcanic rocks in the Erlian Basin and adjacent areas, Northeast China: new geochemistry, geochronology and zircon Hf isotope constraints on petrogenesis and tectonic setting - Jianzhou Tang; Zhicheng Zhang; Zejia Ji; Yan Chen; Ke Li; Yang Jinfu; Pingping Liu (International Geology Review, 2019)

DNA methylation of CRB3 is a prognostic biomarker in clear cell renal cell carcinoma - Pingping Li; Jie Liu; Juan Li; Peijun Liu (Molecular Biology Reports, 2019)

Correction to: In Vitro Seeding Activity of Glycoform-Deficient Prions from Variably Protease-Sensitive Prionopathy and Familial CJD Associated with PrPV180I Mutation - Zerui Wang; Jue Yuan; Pingping Shen; Romany Abskharon; Yue Lang; Johnny Dang; Alise Adornato; Ling Xu; Jiafeng Chen; Jiachun Feng; Mohammed Moudjou; Tetsuyuki Kitamoto; et al. (Molecular Neurobiology, 2019)

In Vitro Seeding Activity of Glycoform-Deficient Prions from Variably Protease-Sensitive Prionopathy and Familial CJD Associated with PrPV180I Mutation - Zerui Wang; Jue Yuan; Pingping Shen; Romany Abskharon; Yue Lang; Johnny Dang; Alise Adornato; Ling Xu; Jiafeng Chen; Jiachun Feng; Mohammed Moudjou; Tetsuyuki Kitamoto; et al. (Molecular Neurobiology, 2019)

Decreased decidual epithelial sodium channel (ENaC) alpha and gamma subunits in recurrent pregnancy loss (RPL) - Tiantian Yu; Chun Feng; Pingping Lv; Gufeng Xu; Lihua Hong; Yimeng Xiong; Xiaoyan Guo; Tong Li; Jianzhong Sheng; Hefeng Huang; Xinmei Liu (Science China Life Sciences, 2019)

Is phosphorus a limiting factor to regulate the growth of phytoplankton in Daya Bay, northern South China Sea: a mesocosm experiment - Xingyu Song; Meiting Tan; Ge Xu; Xinying Su; Jihua Liu; Gaungyan Ni; Yao Li; Yehui Tan; Liangmin Huang; Pingping Shen; Gang Li (Ecotoxicology, 2019)

Complement Complex C5b-9 Levels Are Associated with the Clinical Outcomes of Acute Ischemic Stroke and Carotid Plaque Stability - Weixin Si; Pingping He; Yi Wang; Yu Fu; Xin Li; Xiaoru Lin; Fenghua Chen; Guodong Cao; Hong Zhang (Translational Stroke Research, 2019)

Trend analysis and modeling of nutrient concentrations in a preliminary eutrophic lake in China - Xinnan Tong; Xinze Wang; Zekun Li; Pingping Yang; Ming Zhao; Kaiqin Xu (Environmental Monitoring and Assessment, 2019)

Effects of Biogas Slurry Application on Crop Production and Soil Properties in a Rice–Wheat Rotation on Coastal Reclaimed Farmland - Yifan Tang; Guoliang Wen; Pingping Li; Cheng Dai; Jiangang Han (Water, Air, & Soil Pollution, 2019)

Species Diversity and Functional Prediction of Soil Bacterial Communities in Constructed Wetlands with Different Plant Conditions - Weiguo Fu; Yuxuan Wang; Wei Wei; Pingping Li (Current Microbiology, 2019)

Evolutionary and functional analyses of the 2-oxoglutarate-dependent dioxygenase genes involved in the flavonoid biosynthesis pathway in tobacco - Zhong Wang; Shanshan Wang; Mingzhu Wu; Zefeng Li; Pingping Liu; Feng Li; Qiansi Chen; Aiguo Yang; Jun Yang (Planta, 2019)

Foliage application of nitrogen has less influence on soil microbial biomass and community composition than soil application of nitrogen - Xingran Huang; Yanfei Liu; Yiyong Li; Pingping Guo; Xiong Fang; Zhigang Yi (Journal of Soils and Sediments, 2019)

Natural and synthetic flavonoids, novel blockers of the volume-regulated anion channels, inhibit endothelial cell proliferation - Yucong Xue; Honglin Li; Yuanyuan Zhang; Xue Han; Gaohua Zhang; Wenya Li; Huiran Zhang; Yue Lin; Pingping Chen; Xiaorun Sun; Yalei Liu; Li Chu; et al. (Pflügers Archiv - European Journal of Physiology, 2018)

Transcriptomic analysis reveals the effect of the exopolysaccharide of Psychrobacter sp. B-3 on gene expression in RAW264.7 macrophage cells - Pingping Zhang; Jiang Li; Leiye Yu; Jingfang Wei; Tong Xu; Guojie Sun (Acta Oceanologica Sinica, 2018)

Crystallization of microporous TiO2 through photochemical deposition of Pt for photocatalytic degradation of volatile organic compounds - Ji Li; Yanhong Wang; Yiyuan Tian; Xuan He; Pingping Yang; Minghui Yuan; Yuqing Cao; Jinze Lyu (Environmental Science and Pollution Research, 2018)

Geological effects influence population genetic connectivity more than Pleistocene glaciations in the water strider Metrocoris sichuanensis (Insecta: Hemiptera: Gerridae) - Zhen Ye; Juanjuan Yuan; Min Li; Jakob Damgaard; Pingping Chen; Chenguang Zheng; Haibin Yu; Siying Fu; Wenjun Bu (Journal of Biogeography, 2018)
Aim Palaeoclimatic and palaeogeological events have been identified as two main factors that influence the genetic structuring of extant organisms. We studied a montane stream‐dwelling insect, Metrocoris sichuanensis , to explore the relative roles played by these two factors in population genetic connectivity. Location Sichuan Basin, China. Methods Mitochondrial ( COI , COII , Cytb, 16S) and nuclear ( EF ‐1α, ITS 1) markers were sequenced from 208 individuals. Suitable habitat shifts from the Last Glacial Maximum ( LGM ) to the present were predicted through fine‐tuned ecological niche modelling ( ENM ). Phylogenetic and phylogeographical analyses were conducted to reveal the population genetic structure. Intraspecific divergence and expansion times were estimated using beast . Finally, the least cost path ( LCP ) method coupled with migrate analysis was used to identify possible dispersal corridors and estimate the asymmetric gene flow. Results Our ENM results suggested that population habitat connectivity did not change both in the LGM and current conditions. Whole haplotypes were separated into four highly supported clades/haplogroups that exhibited strong geographical structure. The splitting events between the four lineages likely date back to the Early Pleistocene. Bayesian skyline plot ( BSP ) indicated a moderate demographic growth from the LGM to the present. A putative dispersal corridor was detected along the Longmen Mountains thrust belt, with unidirectional gene flow from north to south. Main conclusion Our findings support the geographical isolation of the genetic lineages and a deep early Pleistocene split in M. sichuanensis . Landscape connectivity analysis incorporating the genetic data and the ENM prediction revealed that population genetic connectivity was strongly associated with stable climatic habitats shaped by complex topography. The drainage system might have assisted the rapid movement of populations along the Longmen Mountains thrust belt. A strategy for researching the population genetic connectivity of narrow endemics, such as M. sichuanensis , in global biodiversity hotspots is proposed and discussed in this paper.

Limit analysis approach for accessing stability of three-dimensional (3-D) slopes reinforced with piles - Pingping Rao; Linxue Zhao; Qingsheng Chen; Lin Li (Marine Georesources & Geotechnology, 2017)

Light irradiation helps magnetotactic bacteria eliminate intracellular reactive oxygen species - Kefeng Li; Pingping Wang; Chuanfang Chen; Changyou Chen; Lulu Li; Tao Song (Environmental Microbiology, 2017)
Summary Magnetotactic bacteria (MTB) demonstrate photoresponse. However, little is known about the biological significance of this behaviour. Magnetosomes exhibit peroxidase‐like activity and can scavenge reactive oxygen species (ROS). Magnetosomes extracted from the Magnetospirillum magneticum strain AMB‐1 show enhanced peroxidase‐like activity under illumination. The present study investigated the effects of light irradiation on nonmagnetic (without magnetosomes) and magnetic (with magnetosomes) AMB‐1 cells. Results showed that light irradiation did not affect the growth of nonmagnetic and magnetic cells but significantly increased magnetosome synthesis and reduced intracellular ROS level in magnetic cells. Quantitative reverse transcription polymerase chain reaction (qRT‐PCR) was performed to analyse the expression level of magnetosome formation‐associated genes ( mamA , mms6 , mms13 and mmsF ) and stress‐related genes ( recA , oxyR , SOD , amb0664 and amb2684 ). Results showed that light irradiation upregulated the expression of mms6 , mms13 and mmsF . Furthermore, light irradiation upregulated the expression of stress‐related genes in nonmagnetic cells but downregulated them in magnetic cells. Additionally, magnetic cells exhibited stronger phototactic behaviour than nonmagnetic ones. These results suggested that light irradiation could heighten the ability of MTB to eliminate intracellular ROS and help them adapt to lighted environments. This phenomenon may be related to the enhanced peroxidase‐like activity of magnetosomes under light irradiation.

Colon-Targeted Delivery of IgY Against Clostridium difficile Toxin A and B by Encapsulation in Chitosan-Ca Pectinate Microbeads - Pingping Xing; Yanan Shi; Chuangchuang Dong; Hong Liu; Yan Cheng; Junbo Sun; Dalei Li; Min Li; Kaoxiang Sun; Dongxiao Feng (AAPS PharmSciTech, 2017)

Resveratrol Pretreatment Decreases Ischemic Injury and Improves Neurological Function Via Sonic Hedgehog Signaling After Stroke in Rats - Pingping Yu; Li Wang; Fanren Tang; Li Zeng; Luling Zhou; Xiaosong Song; Wei Jia; Jixiang Chen; Qin Yang (Molecular Neurobiology, 2017)

Degradation of triclosan in the presence of p-aminobenzoic acid under simulated sunlight irradiation - Pingping Zhai; Xuan Chen; Wenbo Dong; Hongjing Li; Jean-marc Chovelon (Environmental Science and Pollution Research, 2017)

Degradation of cyflumetofen and formation of its main metabolites in soils and water/sediment systems - Pingping Wang; Minmin Li; Xingang Liu; Jun Xu; Fengshou Dong; Xiaohu Wu; Yongquan Zheng (Environmental Science and Pollution Research, 2016)

Extending the linker region increases the activity of the Bacillus subtilis cellulase CelI15 - Pingping Li; Yang Zhou; Qian Li; Chong Zhang; Zhaowei Sun; Liuyang Tian; Haibo Weng (Biotechnology Letters, 2016)

Mechanical Testing of Tomato Plant Stem in Relation to Structural Composition - Xiliang Zhang; Qian Guo; Yunfeng Xu; Pingping Li; Cheng Chen; Shuo Wu (Agricultural Research, 2016)

Development of genic SSR markers from an assembled Saccharina japonica genome - Jie Peng; Linan Zhang; Xiaojie Li; Cuiju Cui; Ruina Wu; Pingping Tian; Yan Li; Yanling Liu (Journal of Applied Phycology, 2016)

Transplantation of mesenchymal stem cells improves type 1 diabetes mellitus - Lisha Li; Furong Li; Feng Gao; Yali Yang; Yuanyuan Liu; Pingping Guo; Yulin Li (Cell and Tissue Research, 2016)

Bioactive cyclolanstane-type saponins from the stems of Astragalus membranaceus (Fisch.) Bge. var. mongholicus (Bge.) Hsiao - Tingting Wang; Jingya Ruan; Xiaoxia Li; Liping Chao; Pingping Shi; Lifeng Han; Yi Zhang; Tao Wang (Journal of Natural Medicines, 2016)

Degradation of sunscreen agent p-aminobenzoic acid using a combination system of UV irradiation, persulphate and iron(II) - Yicen Xue; Wenbo Dong; Xiaoning Wang; Wenlong Bi; Pingping Zhai; Hongjing Li; Minghua Nie (Environmental Science and Pollution Research, 2016)

Composition and distribution of planktonic ciliates in the southern South China Sea during late summer: Comparison between surface and 75 m deep layer - Huaxue Liu; Pingping Shen; Chunhou Li; Zuozhi Chen; Zhanhui Qi; Honghui Huang (Journal of Ocean University of China, 2016)

Persistence Parameter: a Reliable Measurement for Behavioral Responses of Medaka (Oryzias latipes) to Environmental Stress - Li Yin; Haitang Yang; Guiyun Si; Qing Ren; Rongshu Fu; Biao Zhang; Xu Zhang; Xiaoguang Wang; Pingping Qi; Chunlei Xia; Zongming Ren; Tae-Soo Chon; et al. (Environmental Modeling & Assessment, 2016)

A novel l-asparaginase from Aquabacterium sp. A7-Y with self-cleavage activation - Zhibin Sun; Ding Li; Pingping Liu; Wenhui Wang; Kai Ji; Yan Huang; Zhongli Cui (Antonie van Leeuwenhoek, 2016)

A novel dual EGFR/HER2 inhibitor KU004 induces cell cycle arrest and apoptosis in HER2-overexpressing cancer cells - Chongchong Tian; Pingping Ding; Ziqiao Yuan; Han Li; Yanxia Zhao; Lan Sun; Qingming Guo; Zhenzhong Wang; Lixin Sun; Luyong Zhang; Zhenzhou Jiang (Apoptosis, 2015)

Downregulation of the lycopene ε-cyclase gene confers tolerance to salt and drought stress in Nicotiana tabacum - Yanmei Shi; Pingping Liu; Yuzhen Xia; Pan Wei; Wenzheng Li; Wei Zhang; Xia Chen; Peijian Cao; Yalong Xu; Lifeng Jin; Feng Li; Zhaopeng Luo; et al. (Acta Physiologiae Plantarum, 2015)

Degradation of organic ultraviolet filter diethylamino hydroxybenzoyl hexyl benzoate in aqueous solution by UV/H2O2 - Ping Gong; Haixia Yuan; Pingping Zhai; Wenbo Dong; Hongjing Li (Environmental Science and Pollution Research, 2015)

BTG3 upregulation induces cell apoptosis and suppresses invasion in esophageal adenocarcinoma - Yuwen Du; Pingping Liu; Wenqiao Zang; Yuanyuan Wang; Xiaonan Chen; Min Li; Guoqiang Zhao (Molecular and Cellular Biochemistry, 2015)

Detection of inherited mutations for hereditary cancer using target enrichment and next generation sequencing - Yanfang Guan; Hong Hu; Yin Peng; Yuhua Gong; Yuting Yi; Libin Shao; Tengfei Liu; Gairui Li; Rongjiao Wang; Pingping Dai; Yves-Jean Bignon; Zhe Xiao; et al. (Familial Cancer, 2015)

PI3K/Akt/uncoupling protein 2 signaling pathway may be involved in cell senescence and apoptosis induced by angiotensin II in human vascular endothelial cells - Ping Li; Xin Guo; Pingping Lei; Shoujun Shi; Shike Luo; Xiaoshu Cheng (Molecular Biology Reports, 2014)

Development of 27 trinucleotide microsatellite markers for Saccharina japonica using next generation sequencing technology - Linan Zhang; Jie Peng; Xiaojie Li; Yanling Liu; Cuiju Cui; Hao Wu; Ruina Wu; Pingping Tian; Yan Li (Conservation Genetics Resources, 2014)

Predation pressure induced by seasonal fishing moratorium changes the dynamics of subtropical Cladocera populations - Qiuqi Lin; Pingping Zhao; Qiuting Wu; Zhihong Wei; Huiming Li; Bo-Ping Han (Hydrobiologia, 2013)

Variations in silicate concentration affecting photosynthetic carbon fixation by spring phytoplankton assemblages in surface water of the Strait of Malacca - Gang Li; Qiang Lin; Pingping Shen; Guangyan Ni; Xingyu Song; Shengfu Wang; Yanzhi Fan; Liangmin Huang; Yehui Tan (Acta Oceanologica Sinica, 2013)

Longitudinal patterns of spring-intermonsoon phytoplankton biomass, species compositions and size structure in the Bay of Bengal - Gang Li; Zhixin Ke; Qiang Lin; Guangyan Ni; Pingping Shen; Huaxue Liu; Jianqiang Yin; Kaizhi Li; Liangmin Huang; Yehui Tan (Acta Oceanologica Sinica, 2012)

Latitudinal variability (6°S–20°N) of early summer phytoplankton species compositions and size-fractioned productivity from Java Sea to South China Sea - Gang Li; Liangmin Huang; Huaxue Liu; Zhixin Ke; Qiang Lin; Guangyan Ni; Jianqiang Yin; Kaizhi Li; Xingyu Song; Pingping Shen; Yehui Tan (Marine Biology Research, 2012)

Liposomes Containing (-)-Gossypol-Enriched Cottonseed Oil Suppress Bcl-2 and Bcl-xL Expression in Breast Cancer Cells - Hong Li; Longzhu Piao; Pingping Xu; Weiping Ye; Saiyi Zhong; Shu-Hong Lin; Samuel K. Kulp; Yicheng Mao; Youngah Cho; L. James Lee; Robert J. Lee; Young C. Lin (Pharmaceutical Research, 2011)

Potential for forest vegetation carbon storage in Fujian Province, China, determined from forest inventories - Yin Ren; Xiaohua Wei; Li Zhang; Shenghui Cui; Feng Chen; Yongzhu Xiong; Pingping Xie (Plant and Soil, 2011)

Mechanism of the plant community succession process in the Zhenjiang Waterfront Wetland - Weiguo Fu; Pingping Li; Yanyou Wu (Plant Ecology, 2011)

An Experimental Study of the Influence of Interfacial Tension on Water–Oil Two-Phase Relative Permeability - Pingping Shen; Bin Zhu; Xian-Bin Li; Yu-Shu Wu (Transport in Porous Media, 2010)

Involvement of JNK regulation in oxidative stress-mediated murine liver injury by microcystin-LR - Yinna Wei; Dan Weng; Feng Li; Xiao Zou; D. Owen Young; Jianguo Ji; Pingping Shen (Apoptosis, 2008)

Impact of Zn, Cu, and Fe on the Activity of Carbonic Anhydrase of Erythrocytes in Ducks - Yanyou Wu; Xinzhen Zhao; Pingping Li; Huakun Huang (Biological Trace Element Research, 2007)

Comparison of carbonic anhydrase activity among various species of plantlets - Wu Yanyou; Li Xiteng; Li Pingping; Zhao Xinzheng (Plant Cell, Tissue and Organ Culture (PCTOC), 2006)

D-Galactose-caused life shortening in Drosophila melanogaster and Musca domestica is associated with oxidative stress - Xu Cui; Luning Wang; Pingping Zuo; Zhitao Han; Zhengyu Fang; Wenbin Li; Jiankang Liu (Biogerontology, 2004)